High-strength aluminum alloy for can end blank and preparation method of high-strength aluminum alloy
By adjusting the aluminum alloy composition and process, the problems of recycling and mechanical properties of recycled aluminum alloy materials in the production of can end blanks were solved, achieving high recycling rate and low cost aluminum alloy production, and meeting the strength and formability requirements of can end blanks.
Patent Information
- Application Number
- CN202380038068.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-04
- Filing Date
- 2023-05-02
- Publication Date
- 2025-02-28
AI Technical Summary
Existing technologies make it difficult to effectively utilize recycled aluminum alloy materials to produce can end blanks, resulting in low recyclability of recycled aluminum alloy products, the need to add primary aluminum, increased costs, and environmental hazards. Furthermore, a large component of recycled materials affects mechanical properties.
By adjusting the composition of aluminum alloys, including 0.10-0.35 wt% Si, 0.20-0.60 wt% Fe, 0.05-0.25 wt% Cu, 0.25-1.20 wt% Mn, 1.3-5.0 wt% Mg, up to 0.20 wt% Cr, up to 0.30 wt% Zn, up to 0.20 wt% Ti, up to 0.15 wt% impurities and Al, and combining homogenization and hot-rolling/cold-rolling processes, the particle size and composition in the microstructure of the aluminum alloy are controlled to form α-phase particles.
It enables the production of high-strength and formable aluminum alloys using more recycled aluminum materials, reducing primary aluminum usage, lowering costs, and maintaining the same mechanical properties as traditional aluminum alloys, making it suitable for the production of can end blanks.
Smart Images

Figure CN119546791A_ABST
Abstract
Description
[0001] Citation of Related Applications
[0002] This application claims the benefit of and priority to U.S. Provisional Patent Application No. 63 / 364,163, filed on May 4, 2022, the contents of which are hereby incorporated by reference in their entirety for all intents and purposes. Technical Field
[0003] The present disclosure relates to metallurgy, aluminum alloys, aluminum processing and related fields. In particular, the present disclosure provides a novel aluminum alloy with a large amount of recycled aluminum material, which can be used to produce can end stock. The present disclosure also relates to a method for producing a novel aluminum alloy from recycled aluminum alloy material, the method providing control over the particle size of components in the aluminum alloy microstructure, thereby improving the mechanical properties of the aluminum alloy. Background Art
[0004] Can end stock is typically made from a high strength aluminum alloy with good formability characteristics. The mechanical requirements of the aluminum alloy used to produce the can end stock are different from those of the can body stock. Generally speaking, the aluminum alloy used to produce the can end stock requires greater strength than the can body stock. Therefore, can end stock is typically made from an aluminum alloy containing a large amount of magnesium (Mg). For example, can end stock can be made from a highly engineered AA5182 aluminum alloy, which has a strictly controlled composition and process for producing the alloy.
[0005] Many aluminum manufacturers use the same alloy for can end stock. Attempts to change the aluminum alloy composition of can end stock have not been successful, mainly because changes in the aluminum alloy composition can significantly affect mechanical properties (such as strength and formability). For example, the composition of AA5182 aluminum alloy is strictly controlled to have a Mg content between 4.0 wt% and 5.0 wt%, a manganese (Mn) content between 0.20 wt% and 0.50 wt%, a maximum iron (Fe) content of 0.35 wt%, a maximum silicon (Si) content of 0.20 wt%, a maximum copper (Cu) content of 0.15 wt%, and a maximum chromium (Cr) content of 0.10 wt%. However, recycled materials, such as used beverage cans (UBC), are not used to produce can end stock and can body stock because UBC contains two separate aluminum alloys with different aluminum alloy compositions. Specifically, can end stock is typically produced from AA5182 aluminum alloy, while can body stock is typically produced from AA3104 aluminum alloy. Since there are two different aluminum alloys in UBC, there is little commonality in the composition of the new aluminum alloy used to make the can body stock and can end stock. Therefore, if the new aluminum alloy is produced using UBC, it is necessary to add primary aluminum and other alloying elements to adjust the composition used to produce the can end stock and can body stock. This reduces the recyclability of the recycled aluminum alloy product for the production of new aluminum alloys and requires the addition of primary aluminum, which reduces the recycled content. In addition, the additional primary aluminum increases carbon dioxide production and increases costs, resulting in environmental harm and high costs.
[0006] In addition, aluminum alloys produced from high-content recycled aluminum materials usually contain a large amount of alloying elements. Alloying elements can produce large components in the aluminum alloy microstructure that are difficult to decompose and have a negative impact on the mechanical properties of the aluminum alloy. For example, large amounts of Si, Fe and / or Mn (which are common alloying elements in recycled aluminum alloy materials) can produce large components (such as Al) in the aluminum alloy microstructure. x (Fe, Mn)), which is a large component that cannot be fully processed or decomposed during the production of the aluminum alloy (for example, the large component is not easily decomposed during rolling deformation). Therefore, the large component still remains in the aluminum alloy microstructure of the aluminum alloy product (for example, a sheet) after production. The large component in the aluminum alloy microstructure can have a negative impact on, for example, the formability of the aluminum alloy. Summary of the invention
[0007] The embodiments covered by the present disclosure are defined by the claims rather than by this Summary. This Summary is a high-level overview of various aspects of the invention and introduces some concepts that are further described in the Detailed Description section below. This Summary is not intended to identify the key features or essential features of the claimed subject matter, nor is it intended to be used alone to determine the scope of the claimed subject matter. The subject matter should be understood by reference to appropriate portions of the entire specification, any or all of the drawings, and each claim.
[0008] The aluminum alloys described herein provide a more cost-effective and recycling-friendly material alternative to using AA5182 alloy for can end stock. In some embodiments, the present disclosure relates to an aluminum alloy comprising 0.10-0.35 wt % Si, 0.20-0.60 wt % Fe, 0.05-0.25 wt % Cu, 0.25-1.20 wt % Mn, 1.3-5.0 wt % Mg, up to 0.20 wt % Cr, up to 0.30 wt % Zn, up to 0.20 wt % Ti, up to 0.15 wt % impurities, and Al. In some embodiments, the present disclosure relates to an aluminum alloy comprising 0.10-0.35 wt % Si, 0.20-0.60 wt % Fe, 0.05-0.25 wt % Cu, 0.25-1.20 wt % Mn, 2.0-5.0 wt % Mg, up to 0.20 wt % Cr, up to 0.30 wt % Zn, up to 0.20 wt % Ti, up to 0.15 wt % impurities and Al. In some aspects, the aluminum alloy comprises 0.10-0.30 wt % Si, 0.20-0.50 wt % Fe, 0.05-0.25 wt % Cu, 0.30-1.0 wt % Mn, 2.2-5.0 wt % Mg, up to 0.15 wt % Cr, up to 0.30 wt % Zn, up to 0.15 wt % Ti, up to 0.15 wt % impurities and Al. In some aspects, the aluminum alloy comprises 0.10-0.25 wt % Si, 0.20-0.50 wt % Fe, 0.05-0.25 wt % Cu, 0.30-0.90 wt % Mn, 2.5-5.0 wt % Mg, up to 0.10 wt % Cr, up to 0.25 wt % Zn, up to 0.10 wt % Ti, up to 0.15 wt % impurities and Al. In some aspects, the aluminum alloy comprises 0.20-0.35 wt % Si, 0.20-0.50 wt % Fe, 0.05-0.25 wt % Cu, 0.30-0.90 wt % Mn, 2.5-5.0 wt % Mg, up to 0.05 wt % Cr, up to 0.25 wt % Zn, up to 0.05 wt % Ti, up to 0.15 wt % impurities and Al. In some aspects, the aluminum alloy comprises 0.20-0.35 wt % Si, 0.40-0.60 wt % Fe, 0.15-0.25 wt % Cu, 0.60-1.2 wt % Mn, 2.0-4.0 wt % Mg, up to 0.03 wt % Cr, up to 0.20 wt % Zn, up to 0.03 wt % Ti, up to 0.15 wt % impurities and Al. In some aspects, the ratio of Mg:Cu is 10:1 to 80:1, and the ratio of Mn:Cu is 2:1 to 15:1. In some aspects, the ratio of Mg:Cu is 15:1 to 70:1, and the ratio of Mn:Cu is 3:1 to 12:1.In some aspects, the aluminum alloy has a combined content of Fe and Si greater than 0.40 wt %. In some aspects, the aluminum alloy has a combined content of Mg, Mn and Cu of 3.5 wt % to 5.0 wt %. In some aspects, the aluminum alloy comprises at least 40 wt % of recycled scrap. In some aspects, the aluminum alloy has less than 30 wt % of raw aluminum. In some aspects, the aluminum alloy has at least 30.0 KJ / m measured by ASTM B871-1 (2021). 2 In some aspects, the aluminum alloy has a yield strength of at least 340 MPa. In some aspects, the aluminum alloy has an ultimate tensile strength of at least 380 MPa. In some aspects, the aluminum alloy has a total elongation of at least 4%. In some aspects, the can end stock comprises any of the foregoing aluminum alloys.
[0009] In some embodiments, a method for producing an aluminum alloy is provided. The method includes casting an aluminum alloy to form a cast product, wherein the aluminum alloy contains 0.10-0.35 wt. % Si, 0.20-0.60 wt. % Fe, 0.05-0.25 wt. % Cu, 0.25-1.20 wt. % Mn, 2.0-5.0 wt. % Mg, up to 0.20 wt. % Cr, up to 0.30 wt. % Zn, up to 0.20 wt. % Ti, up to 0.15 wt. % impurities and Al; homogenizing the cast product; hot rolling the cast product to produce a hot rolled product; cold rolling the hot rolled product to produce a final specification rolled product; and optionally annealing the final specification rolled product. In some aspects, the method includes painting and curing the final specification rolled product. In some aspects, the homogenization step includes a first homogenization step and a second homogenization step. In some aspects, the first homogenization step comprises soaking the cast product at a temperature of 375°C to 450°C for 0.5 to 5 hours. In some aspects, the second homogenization step comprises soaking the cast product at a temperature of 450°C to 550°C for 0.01 to 5 hours. In some aspects, the aluminum alloy comprises 0.10-0.25 wt% Si, 0.20-0.50 wt% Fe, 0.05-0.25 wt% Cu, 0.30-0.90 wt% Mn, 2.5-5.0 wt% Mg, up to 0.10 wt% Cr, up to 0.25 wt% Zn, up to 0.10 wt% Ti, up to 0.15 wt% impurities and Al. In some aspects, the ratio of Mg:Cu is 15:1 to 70:1, and the ratio of Mn:Cu is 3:1 to 12:1. In some aspects, the metal product is prepared by the foregoing method. In some aspects, the metal product is a can end blank.
[0010] In some embodiments, the present disclosure provides an aluminum alloy comprising 0.01-0.60 wt % Si, 0.01-0.80 wt % Fe, 0.05-0.30 wt % Cu, 0.80-1.40 wt % Mn, 1.3-5.0 wt % Mg, up to 0.20 wt % Cr, up to 0.30 wt % Zn, up to 0.05 wt % Ti, up to 0.15 wt % impurities, and the remainder of Al. In some embodiments, the aluminum alloy comprises 0.10-0.50 wt % Si, 0.20-0.70 wt % Fe, 0.11-0.30 wt % Cu, 0.80-1.00 wt %. % Mn, 1.5-5.0 wt % Mg, up to 0.20 wt % Cr, up to 0.25 wt % Zn, up to 0.05 wt % Ti, up to 0.15 wt % impurities, and the remainder of Al. In some embodiments, the aluminum alloy comprises 0.22-0.32 wt % Si, 0.50-0.65 wt % Fe, 0.20-0.30 wt % Cu, 0.80-0.92 wt % Mn, 2.0-4.0 wt % Mg, up to 0.20 wt % Cr, up to 0.25 wt % Zn, up to 0.03 wt % Ti, up to 0.15 wt % impurities, and the remainder Al. In some embodiments, the aluminum alloy comprises 0.25-0.32 wt % Si, 0.45-0.55 wt % Fe, 0.20-0.30 wt % Cu, 0.80-0.92 wt % Mn, 2.0-4.0 wt % Mg, 0.01-0.20 wt % Cr, up to 0.25 wt % Zn, up to 0.03 wt % Ti, up to 0.15 wt % impurities, and the remainder Al. In some embodiments, the aluminum alloy comprises 0.25-0.35 wt. % Si, 0.45-0.55 wt. % Fe, 0.16-0.30 wt. % Cu. % Cu, 0.80-0.92 wt. % Mn, 3.0-4.0 wt. % Mg, 0.05-0.15 wt. % Cr, up to 0.25 wt. % Zn, up to 0.03 wt. % Ti, up to 0.15 wt. % impurities, and the remainder Al. In some embodiments, the aluminum alloy comprises 0.05-0.20 wt. % Cr. In some embodiments, the aluminum alloy has a Mg:Cr ratio of 20:1 to 70:1. In some embodiments, the aluminum alloy has a combined content of Si, Cr, and Cu greater than 0.35 wt. %. In some embodiments, the aluminum alloy has a combined content of Fe and Si greater than 0.40 wt. %. In some embodiments, the particles in the aluminum alloy microstructure have a diameter of 1.45 μm measured by area. 2or smaller particle size. In some embodiments, the aluminum alloy comprises at least 40% by weight of recycled scrap. In some embodiments, the aluminum alloy comprises less than 30% by weight of primary aluminum. In some embodiments, the aluminum alloy has a yield strength of at least 340 MPa. In some embodiments, the aluminum alloy has an ultimate tensile strength of at least 380 MPa. In some embodiments, the aluminum alloy has a total elongation of at least 4%. In some embodiments, the can end stock comprises any of the foregoing aluminum alloys.
[0011] In some embodiments, a method for producing an aluminum alloy is provided. The method includes casting an aluminum alloy to form a cast product, wherein the aluminum alloy contains 0.01-0.60 wt% Si, 0.01-0.80 wt% Fe, 0.05-0.30 wt% Cu, 0.80-1.40 wt% Mn, 1.3-5.0 wt% Mg, up to 0.20 wt% Cr, up to 0.30 wt% Zn, up to 0.05 wt% Ti, up to 0.15 wt% impurities, and the remainder Al; homogenizing the cast product, wherein homogenizing the cast product produces α-phase particles; hot rolling the cast product to produce a hot rolled product; cold rolling the hot rolled product to produce a final specification rolled product; and optionally annealing the final specification rolled product. In some embodiments, the aluminum alloy contains 0.05-0.20 wt% Cr, wherein the ratio of Mg:Cr is 20:1 to 70:1. In some embodiments, the homogenization step includes heating and soaking the cast product at a temperature of 450°C to 570°C, wherein the homogenization is configured to transform large particles into alpha phase particles. In some embodiments, the cast product is soaked at the homogenization temperature for up to 10 hours. In some embodiments, the aluminum alloy comprises a particle area percentage of 1.5% or more alpha phase particles measured by volume after homogenization. In some embodiments, the aluminum alloy comprises 0.22-0.32 wt % Si, 0.50-0.65 wt % Fe, 0.20-0.30 wt % Cu, 0.80-0.92 wt % Mn, 2.0-4.0 wt % Mg, up to 0.20 wt % Cr, up to 0.25 wt % Zn, up to 0.03 wt % Ti, up to 0.15 wt % impurities, and the remainder Al.
[0012] Other aspects, objects and advantages will become apparent upon consideration of the following detailed description and accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 A graphical representation of yield stress, ultimate tensile strength, and total elongation for example aluminum alloys according to some embodiments described herein is provided.
[0014] Figure 2A graphical representation of the yield stress (MPa) measured in the longitudinal (L), transverse (T), and diagonal (D) directions (each corresponding to the rolling direction) of example aluminum alloys according to some embodiments described herein is provided.
[0015] Figure 3A and 3B A graphical representation of the particle area % and particle number density of alpha particles, Al(Fe,Mn) particles, and Mg2Si particles in the aluminum alloy microstructure as a function of the Fe and Si concentrations in the example aluminum alloys is provided.
[0016] Figure 4 Provides measurements according to ASTM B873-1(2021) Figure 3A and 3B A graphical representation of the propagated energy and yield stress for the example alloys provided in .
[0017] Figure 5A and 5B A graphical representation of the particle area % and particle number density of α particles, Al(Fe,Mn) particles, and Mg2Si particles in the aluminum alloy microstructure as a function of the Mn concentration in the example aluminum alloy is provided.
[0018] Figure 6 Provides measurements according to ASTM B873-1(2021) Figure 5A and 5B A graphical representation of the propagated energy and yield stress for the example alloys provided in .
[0019] Fig. 7A and 7B A graphical representation of the particle area % and particle number density of α particles, Al(Fe,Mn) particles, and Mg2Si particles in the aluminum alloy microstructure as a function of the Mg concentration in the example aluminum alloy is provided.
[0020] Figure 8 Provides measurements according to ASTM B873-1(2021) Fig. 7A and 7B A graphical representation of the propagated energy and yield stress for the example alloys provided in .
[0021] Fig. 9A and 9B A graphical representation of the particle area % and particle number density of α particles, Al(Fe,Mn) particles, and Mg2Si particles in the aluminum alloy microstructure as a function of the Mg and Mn concentrations in the example aluminum alloys is provided.
[0022] Fig.10 Provides measurements according to ASTM B873-1(2021) Fig. 9A and 9BA graphical representation of the propagated energy and yield stress for the example alloys provided in .
[0023] Fig.11 A graphical representation of the failure strain of a bulge test of an example alloy measured according to ISO 16808 (2021) is provided.
[0024] Fig.12 Buckle strength graphs are provided for example alloys.
[0025] Fig.13A and 13B Provides AA5182 aluminum alloy ( Fig.13A ) and an example aluminum alloy produced from a large amount of recycled aluminum materials ( Fig. 13B ) is a scanning electron microscope (SEM) image of the microstructure.
[0026] Figures 14A-14D Thermodynamic equilibrium calculations performed on Thermo-Calc are provided to show that the particles in the aluminum alloy microstructure vary with Example Alloy 9 ( Fig.14A )、Example Alloy 10( Fig. 14B )、Example Alloy 11( Fig. 14C ) and Example Alloy 12 ( Fig.14D ) is a graphical representation of the homogenization temperature variation.
[0027] Fig.15A and 15B The particle area % ( Fig.15A ) and average particle size ( Fig. 15B ) icon. DETAILED DESCRIPTION
[0028] New aluminum alloy variants that exhibit high strength and formability are described herein. Surprisingly, the aluminum alloys described herein exhibit high strength and formability despite having a lower Mg content than the conventional AA5182 aluminum alloy used to produce can end billets. The aluminum alloys described herein incorporate greater amounts of recycled aluminum materials and less virgin aluminum than conventional aluminum alloys used to produce can end billets and still maintain good mechanical properties for can end billets. For example, the aluminum alloys described herein may contain more than 40% recycled aluminum alloy and less than 30% virgin aluminum than conventional aluminum alloys used to produce can end billets and still exhibit properties comparable to those of the AA5182 aluminum alloy. The aluminum alloy compositions described throughout this article provide a cost-effective alternative to using the AA5182 aluminum alloy for can end billets.
[0029] Conventional AA5182 aluminum alloys for producing can end stock require strictly controlled composition to meet the minimum strength requirements of the can end stock while still maintaining formability to produce complex geometries. In general, the aluminum alloys used to produce can end stock need to have higher strength than can body stock, which indicates that such can end stock must be made of aluminum alloys (such as AA5182 aluminum alloys) containing a large amount of Mg. This limits the amount of recycled aluminum materials that can be used to produce AA5182 aluminum alloys. For example, AA5182 aluminum alloys cannot be produced from a large number of waste beverage cans because AA5182 aluminum alloys contain less Fe, Si, Mn and Cu than waste beverage cans. Waste beverage cans contain a mixture of two different aluminum alloys for can body stock and can end stock. The aluminum alloy used for can end stock is generally AA5182 aluminum alloy, and the aluminum alloy used for can body stock is generally AA3104 aluminum alloy. Compared with AA5182 aluminum alloy, AA3104 aluminum alloy contains less Mg and more Fe, Si, Mn and Cu. Due to the difference between the aluminum alloy composition of AA3104 aluminum alloy and AA5182 aluminum alloy, the aluminum alloy composition of waste beverage cans is between the composition of AA3104 aluminum alloy and AA5182 aluminum alloy. Therefore, in order to produce can end blanks with a large amount of recycled materials (such as waste beverage cans), more alloying elements (such as adding Mg) and raw aluminum are needed to produce AA5182 aluminum alloy, which significantly increases the material cost. This limits the amount of recycled aluminum materials that can be used to produce can end blanks.
[0030] The new aluminum alloy described herein can utilize a larger amount of recycled aluminum materials and achieve similar properties to AA5182 aluminum alloy. Specifically, compared with AA5182 aluminum alloy, the aluminum alloy described herein can tolerate a larger amount of Fe, Si, Mn and / or Cu, and still achieve good strength and formability characteristics. In addition, the aluminum alloy described herein may contain a smaller amount of Mg, which can be compensated by adding elements such as Mn and Cu to balance strength. The aluminum alloy composition described herein reduces the composition gap between the can body blank and the can end blank to reduce the amount of original aluminum and reduce the addition of alloying elements (e.g., Mg). By reducing the composition gap between the can body blank and the can end blank aluminum alloy, more recycled aluminum alloys (e.g., waste beverage cans) can be used to produce aluminum alloys for can end blanks. For example, the aluminum alloy described herein can be produced by at least 40% by weight of recycled scrap and less than 30% by weight of original aluminum.
[0031] In addition, the aluminum alloy composition produces can end stock with similar properties to conventional AA5182 aluminum alloy, allowing can manufacturers to produce aluminum alloys without changing existing processes. In some embodiments, a larger amount of waste beverage cans can be used with the aluminum alloys described herein, thereby reducing the amount of raw aluminum required and reducing overall costs while maintaining equal or better rolling productivity.
[0032] The aforementioned aluminum alloy compositions have processing advantages despite having a large amount of recycled aluminum alloys, which is a common problem in making new aluminum alloys using a large amount of recycled aluminum alloys. Specifically, the amount of Mg in the aluminum alloy composition can be naturally reduced to about 1 wt. % Mg by fluxing, degassing, and dross treatment during the remelting process. Therefore, the final molten aluminum alloy composition can be very similar to AA3104 aluminum alloy. The aluminum alloy described herein can be reused to make can body blanks. In addition, by appropriately adjusting the Mg content, the aluminum alloy described herein can also be recycled for the production of can end blanks. Advantageously, this allows closed-loop recycling of used beverage cans (UBC) produced from the aluminum alloy composition described herein. In this way, UBC waste can be continuously reused in a closed-loop system to produce aluminum alloys without major changes in alloying elements. That is, aluminum alloy products (e.g., UBC) made from the aluminum alloy composition described herein can be used to produce new aluminum alloys for can end blanks or can body blanks. Furthermore, since the Fe, Si, Cu and Mn levels in UBC scrap are similar to the aluminum alloy compositions described herein, only additional Mg needs to be added to the aluminum alloy to produce can end stock from UBC.
[0033] In some embodiments, the present disclosure relates to an aluminum alloy having a composition similar to that of an AA3104 aluminum alloy (except for Mg) and exhibiting properties similar to those of an AA5182 aluminum alloy (e.g., buckling strength). For example, the aluminum alloy may contain Fe, Si, Cu, and Mn contents similar to those of an AA3104 aluminum alloy, and may contain a Mg content greater than 2.0 wt%. The aluminum alloy may contain a large amount of recycled materials and achieve properties similar to those of an AA5182 aluminum alloy. In some embodiments, the aluminum alloy described herein may have a composition similar to that of an AA3104 aluminum alloy, may contain a Mg content of 2.0 wt% to 4.0 wt%, and exhibit a buckling strength greater than 90 psi. Advantageously, the aluminum alloy includes Fe, Si, Cu, and Mn in similar amounts to the AA3104 aluminum alloy used for UBC. Therefore, UBC scrap can be used almost entirely to produce the aluminum alloy, thereby eliminating the need to dilute the aluminum alloy with raw aluminum or to add alloying elements for hardening. This provides an aluminum alloy that can contain a larger amount of UBC scrap and less raw aluminum, and contains very little or no other alloying elements except Mg. Advantageously, the aluminum alloy can contain a Mg content that meets the strength requirements of the can end billet. If UBC scrap is used to produce an aluminum alloy without adding Mg, the strength of the resulting aluminum alloy may be greatly reduced, and insufficient buckling strength (e.g., shell buckling strength and can end buckling strength) may result. Compared to AA3104 aluminum alloy, the aluminum alloy described herein may contain a larger amount of Mg to meet the minimum strength requirements of the can end billet. In some embodiments, the aluminum alloy described herein may have a composition similar to that of AA3104 aluminum alloy, and may contain a Mg content greater than 1.3 wt% (e.g., 1.3 wt% to 2.0 wt% Mg). The aluminum alloy may be used for applications with lower strength requirements.
[0034] In order to maintain a high level of recycled content in the aluminum alloy composition described herein, the aluminum alloy composition can be similar to AA3104 aluminum alloy. For example, Mg can be the main alloying element added to the aluminum alloy composition, and the remaining alloying elements can be similar to AA3104 aluminum alloy. Therefore, it may not be necessary to add other hardening alloying elements (such as Mn and Cu) to the aluminum alloy composition. This is advantageous because the hardening alloying elements (such as Mn and Cu) will not oxidize during the remelting process, thereby affecting the recyclability of the can body aluminum alloy or UBC composition. By maintaining an aluminum alloy composition similar to AA3104 aluminum alloy, the remelting process can be simplified and the need to change the aluminum alloy during manufacturing can be reduced. The aluminum alloy composition described herein contains a higher level of recycled content and less raw aluminum, while also exhibiting mechanical properties similar to the aluminum alloy composition currently used for can end billets (for example, similar to AA5182 aluminum alloy).
[0035] In some embodiments, the present disclosure provides a novel method for manufacturing an aluminum alloy produced from a large amount of recycled aluminum alloy materials (e.g., compared to AA5182 aluminum alloy). Advantageously, the aluminum alloy composition described herein includes a specific combination of alloying elements to produce α-phase particles during carefully controlled homogenization practices. For example, by reducing the Mg content and / or adding Cr (e.g., up to 0.20 wt. %) in the aluminum alloy composition, the aluminum alloy can be homogenized over a wider homogenization temperature range to produce a higher volume fraction of α-phase particles (e.g., compared to other aluminum alloys that do not include the same alloying element composition combination). Control of the homogenization temperature and the aluminum alloy composition can maximize the formation of α particles. For example, compared to an aluminum alloy also produced from a large amount of recycled aluminum alloy materials, the aluminum alloy described herein contains a higher volume fraction of α particles. The α-phase particles include a phase (e.g., a eutectic phase) that can be decomposed into smaller particles during hot rolling, thereby producing an aluminum alloy with good formability and mechanical properties.
[0036] Aluminum alloys produced from large amounts of recycled aluminum alloy materials contain large components in the aluminum alloy microstructure that are difficult to decompose and can negatively affect the mechanical properties of the aluminum alloy. For example, large amounts of Si, Fe, and / or Mn, which are common alloying elements in recycled aluminum alloy materials, can produce large components (such as Al) in the aluminum alloy microstructure. x (Fe, Mn)), which is a large component that cannot be fully processed or decomposed during aluminum alloy production. The particle size and number density of the components in the aluminum alloy microstructure partially determine the formability and performance of the aluminum alloy. Therefore, particle size control is beneficial for producing aluminum alloys with desired mechanical properties.
[0037] The aluminum alloys described herein have carefully controlled amounts of Si, Mg, Cu, and Cr and are produced according to the methods described herein, providing an aluminum alloy microstructure containing a greater amount of α-phase particles and a lesser amount of large components than other aluminum alloys produced from recycled aluminum alloy materials. Specifically, by varying the alloying elements and homogenizing at a temperature at which an α-phase transformation occurs, the aluminum alloys have a microstructure containing a high number density of small particles. The aforementioned aluminum alloys have a wide range of homogenization temperature ranges that can transform large particles into particles such as Al x (Fe, Mn) α-phase particles. In addition, the aluminum alloy is homogenized at a homogenization temperature, which converts the large components into α-phase particles. In some embodiments, the aforementioned aluminum alloy may be homogenized at a temperature range of 450° C. to 570° C. to provide a higher volume fraction of α-phase particles than other aluminum alloys produced from recycled aluminum alloy materials. The α-phase particles produced during homogenization can be decomposed into smaller particles during hot rolling, thereby significantly improving formability.
[0038] Definition and Description
[0039] As used herein, the terms "invention," "the invention," "this invention," and "the present invention" are intended to refer broadly to the subject matter of this patent application and the claims that follow in their entirety. Statements containing these terms should not be construed as limiting the subject matter described herein, or limiting the meaning or scope of the patent claims that follow.
[0040] In this specification, reference is made to alloys identified by aluminum industry designations such as "Series" or "5xx." For an understanding of the numerical designation system most commonly used in naming and identifying aluminum and its alloys, refer to "International Alloy Designations and Chemical Limitations for Wrought Aluminum and Wrought Aluminum Alloys" or "The Aluminum Association Register of Alloy Designations and Chemical Limitations for Aluminum Alloys in Casting and Ingot Form," both published by the Aluminum Association.
[0041] As used herein, the meaning of "a", "an" or "the" includes both singular and plural referents unless the context clearly indicates otherwise.
[0042] As used herein, a plate generally has a thickness greater than about 15 mm. For example, a plate may refer to an aluminum product having a thickness greater than about 15 mm, greater than about 20 mm, greater than about 25 mm, greater than about 30 mm, greater than about 35 mm, greater than about 40 mm, greater than about 45 mm, greater than about 50 mm, or greater than about 100 mm.
[0043] As used herein, the thickness of the satt board (also referred to as a sheet board) is generally about 4 mm to about 15 mm. For example, the satt board can have a thickness of about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, about 11 mm, about 12 mm, about 13 mm, about 14 mm, or about 15 mm.
[0044] As used herein, sheet generally refers to an aluminum product having a thickness of less than about 4 mm (eg, less than 3 mm, less than 2 mm, less than 1 mm, less than 0.5 mm, less than 0.3 mm, or less than 0.1 mm). For example, the sheet can have a thickness of about 0.1 mm, about 0.2 mm, about 0.3 mm, about 0.4 mm, about 0.5, about 0.6 mm, about 0.7 mm, about 0.8 mm, about 0.9 mm, about 1 mm, about 1.1 mm, about 1.2 mm, about 1.3 mm, about 1.4 mm, about 1.5 mm, about 1.6 mm, about 1.7 mm, about 1.8 mm, about 1.9 mm, about 2 mm, about 2.1 mm, about 2.2 mm, about 2.3 mm, about 2.4 mm, about 2.5 mm, about 2.6 mm, about 2.7 mm, about 2.8 mm, about 2.9 mm, about 3 mm, about 3.1 mm, about 3.2 mm, about 3.3 mm, about 3.4 mm, about 3.5 mm, about 3.6 mm, about 3.7 mm, about 3.8 mm, about 3.9 mm, or about 4 mm.
[0045] As used herein, formability refers to the ability of a material to be deformed into a desired shape without breaking, tearing, necking, bulging, or forming errors such as wrinkling, springback, or wear. In engineering, formability can be classified according to the deformation mode. Examples of deformation modes include drawing, stretching, bending, and stretch flanging.
[0046] As used herein, primary aluminum refers to an aluminum material containing about at least 99.7% by weight aluminum. Primary aluminum is produced by the initial conversion of raw materials into aluminum (eg, processing bauxite into alumina and electrolyzing the alumina into aluminum).
[0047] As used herein, yield stress (also referred to as yield strength) refers to the point at which an aluminum alloy begins to deform plastically and can no longer return to its original state.
[0048] Reference may be made to alloy states or conditions in this application. For the most commonly used alloy temper descriptions, see "American National Standards (ANSI) H35 on Alloy and Temper Designation Systems". The F state or temper refers to a manufactured aluminum alloy. The O state or temper refers to an aluminum alloy after annealing. The Hxx state or temper, also referred to herein as the H temper, refers to a non-heat-treatable aluminum alloy that has been subjected to or not subjected to heat treatment (e.g., annealing) after cold rolling. Suitable H tempers include HX1, HX2, HX3, HX4, HX5, HX6, HX7, HX8 or HX9 tempers. The T1 state or temper refers to an aluminum alloy that has been cooled from hot working and subjected to natural aging treatment (e.g., at room temperature). The T2 state or temper refers to an aluminum alloy that has been cooled from hot working, cold worked and subjected to natural aging. The T3 state or temper refers to an aluminum alloy that has been solution heat treated, cold worked and naturally aged. The T4 state or temper refers to an aluminum alloy that has been solution heat treated and naturally aged. The T5 temper or temper refers to aluminum alloys that have been cooled from hot working and artificially aged (at elevated temperatures). The T6 temper or temper refers to aluminum alloys that have been solution heat treated and artificially aged. The T7 temper or temper refers to aluminum alloys that have been solution heat treated and artificially overaged. The T8x temper or temper refers to aluminum alloys that have been solution heat treated, cold worked, and artificially aged. The T9 temper or temper refers to aluminum alloys that have been solution heat treated, artificially aged, and cold worked. The W temper or temper refers to aluminum alloys that have been solution heat treated.
[0049] As used herein, "room temperature" may include temperatures from about 15°C to about 30°C, for example, about 15°C, about 16°C, about 17°C, about 18°C, about 19°C, about 20°C, about 21°C, about 22°C, about 23°C, about 24°C, about 25°C, about 26°C, about 27°C, about 28°C, about 29°C or about 30°C.
[0050] All ranges disclosed herein should be understood to encompass both endpoints and any and all subranges included therein. For example, a specified range of "1 to 10" should be considered to include any and all subranges between a minimum of 1 and a maximum of 10 (and including 1 and 10); that is, all subranges start with a minimum of 1 or greater (e.g., 1 to 6.1) and end with a maximum of 10 or less (e.g., 5.5 to 10).
[0051] The following aluminum alloys are described in terms of elemental composition in weight percent (wt%) based on the total weight of the alloy. In certain examples of each alloy, the remainder is aluminum, with a maximum wt% of the sum of impurities of 0.15%.
[0052] Alloy composition
[0053] Aluminum alloy properties are determined in part by the composition of the aluminum alloy. In some aspects, the alloy composition can influence or even determine whether the alloy has the properties suitable for the desired application.
[0054] The alloy described herein is a novel aluminum alloy. The alloy exhibits high strength and high formability (e.g., excellent elongation and forming properties) while containing a greater amount of recycled aluminum alloy. The properties of the alloy are achieved at least in part due to the elemental composition of the alloy. In some cases, the novel aluminum alloy described herein may include a lower Mg content and a higher level of Si and Fe compared to conventional AA5182 aluminum alloy, as further described below.
[0055] In some examples, aluminum alloys as described herein may have the following elemental compositions as provided in Table 1.
[0056] Table 1
[0057]
[0058] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 2.
[0059] Table 2
[0060]
[0061] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 3.
[0062] Table 3
[0063]
[0064] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 4.
[0065] Table 4
[0066]
[0067] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 5.
[0068] Table 5
[0069]
[0070]
[0071] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 6.
[0072] Table 6
[0073]
[0074] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 7.
[0075] Table 7
[0076]
[0077]
[0078] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 8.
[0079] Table 8
[0080]
[0081] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 9.
[0082] Table 9
[0083]
[0084]
[0085] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 10.
[0086] Table 10
[0087]
[0088] Silicon (Si)
[0089] In some examples, the aluminum alloys described herein include Si in an amount of 0.10% to 0.35% (e.g., 0.10% to 0.30%, 0.10% to 0.25%, or 0.20% to 0.35%) based on the total weight of the alloy. For example, the alloy may include 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, or 0.35% Si. All are expressed in weight %. In some embodiments, aluminum alloy compositions containing less than 0.10 wt % Si may limit the amount of recycled aluminum material that can be used for the aluminum alloy composition. For example, AA3104 aluminum alloy used for can body stock typically contains 0.6 wt % Si. In some embodiments, aluminum alloy compositions containing greater than 0.35 wt % Si may form coarse Mg2Si particles in the aluminum alloy microstructure. Coarse Mg2Si particles in the aluminum alloy microstructure may reduce the formability and strength of the aluminum alloy.
[0090] Iron (Fe)
[0091] In some examples, the aluminum alloys described herein further include Fe in an amount of 0.20% to 0.60% (e.g., 0.20% to 0.50%, 0.20% to 0.35%, or 0.40% to 0.60%) based on the total weight of the alloy. For example, the alloy may include 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, or 0.60% Fe. All are expressed in weight %. In some embodiments, an aluminum alloy composition containing less than 0.20 weight % Fe may cause processing defects. For example, due to excessive die build up, the aluminum alloy may have poor runnability. Runnability refers to whether the aluminum alloy includes defects or blockages during the process of producing the aluminum alloy. In addition, the inclusion of less than 0.20 weight % Fe in the aluminum alloy composition may limit the amount of recycled aluminum material that can be used for the aluminum alloy. In some embodiments, aluminum alloy compositions including greater than 0.50 wt. % Fe may result in poor formability due to a large amount of Fe-containing intermetallic particles in the aluminum alloy microstructure.
[0092] Copper (Cu)
[0093] In some examples, the aluminum alloy described herein includes Cu in an amount of 0.05% to 0.25% (e.g., 0.15% to 0.25%) based on the total weight of the alloy. For example, the alloy may include 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, or 0.25% Cu. All are expressed in wt%. As discussed herein, the aluminum alloy may include 0.05% to 0.25% Cu to compensate for the reduced content of Mg, thereby enhancing the strength of the aluminum alloy. In some embodiments, an aluminum alloy including less than 0.05% Cu by weight may result in insufficient strength properties. In some embodiments, aluminum alloys containing greater than 0.25 wt. % Cu may result in excessive strength, poor formability, and susceptibility to corrosion.
[0094] Manganese (Mn)
[0095] In some examples, the aluminum alloys described herein may include Mn in an amount of 0.25% to 1.20% (e.g., 0.30% to 1.0%, 0.30% to 0.90%, or 0.60% to 1.20%) based on the total weight of the alloy. For example, the alloy may include 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.7 2%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, or 1.20% Mn. All are expressed in weight %. As discussed herein, the aluminum alloy may include 0.30% to 1.2% Cu by weight to compensate for the reduced content of Mg, thereby enhancing the strength of the aluminum alloy. In some embodiments, aluminum alloys containing less than 0.30% by weight Mn may result in insufficient strength properties. In some embodiments, aluminum alloys containing greater than 0.90% by weight Mn may result in intermetallic phases, thereby reducing formability and final manufacturing properties.
[0096] Magnesium (Mg)
[0097] In some examples, the aluminum alloys described herein may include Mg in an amount of 2.0% to 5.0% (e.g., 2.2% to 5.0%, 2.5% to 5.0%, or 2.0 to 4.0%) based on the total weight of the alloy. For example, the alloy may include 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9% or 5.0% Mg. All are expressed in weight %. In some embodiments, aluminum alloys containing less than 2.0 wt. % Mg may result in insufficient strength properties. In some embodiments, aluminum alloys containing greater than 5.0 wt. % Mg may result in excessive strength, causing operability problems and increased stress corrosion cracking and terminal softening.
[0098] In some cases, the new aluminum alloys described herein may include a lower Mg content than the Mg content of conventional AA5182 aluminum alloys, and may include a certain amount of one or more of Cu or Mn in addition to other elements. For example, the aluminum alloy may include at least one of the aforementioned amounts of Cu or Mn to compensate for the reduced Mg content in the aluminum alloy. This can avoid adding additional Mg to the aluminum alloy composition, thereby reducing costs.
[0099] Zinc (Zn)
[0100] In some examples, the aluminum alloys described herein include Zn in an amount up to 0.30% (eg, 0.05% to 0.25%, 0.10% to 0.25%, or 0.15% to 0.25%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, or 0.30% Zn. In some cases, there is no Zn in the alloy (i.e., 0%). All are expressed in weight %.
[0101] Chromium (Cr)
[0102] In some examples, the aluminum alloys described herein include Cr in an amount of up to 0.20% (e.g., up to 0.15%, up to 0.10%, up to 0.05%, up to 0.03%, 0.01% to 0.20%, 0.05% to 0.20%, or 0.05% to 0.15%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.20% Cr. In some cases, Cr is absent from the alloy (i.e., 0%). All are expressed in weight %. In some embodiments, adding Cr to the aluminum alloy composition can promote the formation of α-phase particles in the aluminum alloy microstructure. By promoting the transformation of the large component into α-phase particles during homogenization, adding Cr can advantageously optimize the particle size of the aluminum alloy (e.g., reduce the particle size). The particle size and number density of particles in the aluminum alloy microstructure are important factors in determining the formability and performance of the aluminum alloy. In some embodiments, Cr can be added to any of the aluminum alloys in Tables 1-10 to control the particle size formation in the aluminum alloy microstructure.
[0103] Titanium (Ti)
[0104] In some examples, the aluminum alloys described herein include Ti in an amount of up to 0.20% (e.g., up to 0.15%, up to 0.10%, up to 0.05%, or up to 0.03%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.20% Ti. In some cases, there is no Ti in the alloy (i.e., 0%). All are expressed in weight %.
[0105] In some examples, the aluminum alloys described herein may include a combined content of Mg, Mn, and Cu in an amount of 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, or 5.0%. All are expressed in weight %. In some embodiments, an aluminum alloy containing a combined weight % of Mg, Mn, and Cu less than 3.5 weight % may result in insufficient flexural strength. In some embodiments, an aluminum alloy containing a combined weight % of Mg, Mn, and Cu greater than 5.0 weight % may result in excessive strength. In some examples, the aluminum alloys described herein may include a ratio of Mg to Cu (also referred to herein as a Mg:Cu ratio) that may be 12:1 to 80:1 (e.g., from 12:1 to 70:1 to 15:1 to 70:1). For example, the Mg:Cu ratio can be 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1, 31:1, 32:1, 33:1, 34:1, 35:1, 36:1, 37:1, 38:1, 39:1, 40:1, 41:1, 42:1, 43:1, 44:1, 45:1 5:1, 46:1, 47:1, 48:1, 49:1, 50:1, 51:1, 52:1, 53:1, 54:1, 55:1, 56:1, 57:1, 58:1, 59:1, 60:1, 61:1, 62:1, 63:1, 64:1, 65:1, 66:1, 67:1, 68:1, 69:1, 70:1, 71:1, 72:1, 73:1, 74:1, 75:1, 76:1, 77:1, 78:1, 79:1 or 80:1.
[0106] In some examples, the aluminum alloys described herein may include a ratio of Mn to Cu (also referred to herein as a Mn:Cu ratio) that may be 2:1 to 15:1 (e.g., 2:1 to 12:1 or 3:1 to 12:1). For example, the Mn:Cu ratio may be 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, or 15:1.
[0107] Trace Elements
[0108] Optionally, the aluminum alloys described herein may also include other trace elements sometimes referred to as impurities in an amount of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. These impurities may include, but are not limited to, Sc, V, Ni, Hf, Zr, Sn, Ga, Ca, Bi, Na, Pb, or a combination thereof. Thus, Sc, V, Ni, Hf, Zr, Sn, Ga, Ca, Bi, Na, or Pb may be present in the alloy in an amount of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. The sum of all impurities does not exceed 0.15% (e.g., 0.1%). All are expressed in wt %. The remaining percentage of each alloy may be aluminum.
[0109] Aluminum alloy composition based on AA3104 alloy
[0110] The present disclosure also provides aluminum alloys having similar compositions to AA3104 aluminum alloys but with greater amounts of Mg. The aluminum alloys may contain similar Fe, Si, Cu, and Mn contents to AA3104 aluminum alloys, and may contain Mg contents greater than 1.3 wt%. This provides an aluminum alloy that may contain greater amounts of UBC scrap and less raw aluminum than AA3104 aluminum alloys, and contain little or no other alloying elements besides Mg. These aluminum alloys may meet the minimum strength requirements for can end stock.
[0111] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 11.
[0112] Table 11
[0113]
[0114]
[0115] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 12.
[0116] Table 12
[0117]
[0118] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 13.
[0119] Table 13
[0120]
[0121]
[0122] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 14.
[0123] Table 14
[0124]
[0125] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 15.
[0126] Table 15
[0127]
[0128]
[0129] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 16.
[0130] Table 16
[0131]
[0132] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 17.
[0133] Table 17
[0134]
[0135] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 18.
[0136] Table 18
[0137]
[0138] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 19.
[0139] Table 19
[0140]
[0141] In some examples, the aluminum alloys described herein may have the following elemental compositions as provided in Table 20.
[0142] Table 20
[0143]
[0144] Silicon (Si)
[0145] In some examples, the aluminum alloys described herein include Si in an amount of 0.10% to 0.60% (e.g., 0.01% to 0.50%, 0.20% to 0.40%, 0.25% to 0.35%, 0.22% to 0.33%, or 0.25% to 0.32%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, %, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, or 0.60% Si. All are expressed in weight %.
[0146] Iron (Fe)
[0147] In some examples, the aluminum alloys described herein further include Fe in an amount of 0.01% to 0.80% (e.g., 0.05% to 0.70%, 0.10% to 0.50%, 0.40% to 0.60%, 0.45% to 0.55%, 0.50% to 0.65%, or 0.45% to 0.55%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, %. 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, or 0.80% Fe. All are expressed in % by weight.
[0148] Copper (Cu)
[0149] In some examples, the aluminum alloys described herein include Cu in an amount of 0.05 to 0.30% (e.g., 0.05 to 0.25, 0.05 to 0.25, 0.11 to 0.30, 0.20 to 0.30, 0.10% to 0.25%, 0.15% to 0.25%, or 0.16% to 0.20%) based on the total weight of the alloy. For example, the alloy may contain 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, or 0.30% Cu. All are expressed in weight %.
[0150] Manganese (Mn)
[0151] In some examples, the aluminum alloys described herein may include Mn in an amount of 0.80% to 1.40% (eg, 0.80% to 1.20%, 0.80% to 1.10%, or 0.80% to 0.92%) based on the total weight of the alloy. For example, the alloy may include 0.80%, 0.81%, 0.82%, 0.83%, 0.84%, 0.85%, 0.86%, 0.87%, 0.88%, 0.89%, 0.90%, 0.91%, 0.92%, 0.93%, 0.94%, 0.95%, 0.96%, 0.97%, 0.98%, 0.99%, 1.00%, 1.01%, 1.02%, 1.03%, 1.04%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.10%, 1.11%, 1.12%, 1.13%, 1.14%, 1.15%, 1.16%, 1.17%, 1.18%, 1.19%, 1.20%, 1.21%, 1.22%, 1.23%, 1.24%, 1.25%, 1.26%, 1.27%, 1.28%, 1.29%, 1.30%, 1.31%, 1.32%, 1.33%, 1.34%, 1.35%, 1.36%, 1.37%, 1.38%, 1.39%, or 1.40% Mn. All expressed in weight %.
[0152] Magnesium (Mg)
[0153] In some examples, the aluminum alloys described herein include Mg in an amount of 1.3% to 5.0% (e.g., 1.5% to 5.0%, 2.0% to 5.0%, 2.0% to 4.0%, 3.0% to 4.0%, or 1.3% to 2.0%) based on the total weight of the alloy. For example, the alloy may contain 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, or 5.0% Mg. All are expressed in weight %. In some embodiments, for applications requiring lower strength (eg, can body or end stock for water or other low pressure applications), the aluminum alloys described herein may include 1.3% to 2.0% Mg.
[0154] Zinc (Zn)
[0155] In some examples, the aluminum alloys described herein include Zn in an amount up to 0.30% (eg, 0.05% to 0.25%, 0.10% to 0.25%, or 0.15% to 0.25%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, or 0.30% Zn. In some cases, there is no Zn in the alloy (i.e., 0%). All are expressed in weight %.
[0156] Chromium (Cr)
[0157] In some examples, the aluminum alloys described herein include Cr in an amount of up to 0.20% (e.g., up to 0.15%, up to 0.10%, up to 0.05%, up to 0.03%, 0.01% to 0.20%, 0.05% to 0.20%, or 0.05% to 0.15%) based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.20% Cr. In some cases, Cr is absent from the alloy (i.e., 0%). All are expressed in weight %. In some embodiments, adding Cr to the aluminum alloy composition can promote the formation of α-phase particles in the aluminum alloy microstructure. By promoting the transformation of the large component into α-phase particles during homogenization, adding Cr can advantageously optimize the particle size of the aluminum alloy (e.g., reduce the overall particle size). The particle size and number density of particles in the aluminum alloy microstructure are important factors in determining the formability and performance of the aluminum alloy. In some embodiments, Cr can be added to any of the aluminum alloys in Tables 11-20 to control the particle size formation in the aluminum alloy microstructure.
[0158] In some embodiments, the amounts of Cr and Mg are carefully controlled to promote α-phase particles. It was found that adding additional Cr and reducing the amount of Mg in the aforementioned aluminum alloy compositions in Tables 11-20 can advantageously promote the formation of α-phase particles. In some embodiments, the addition of Cr and the reduction of Mg in the aluminum alloy composition can be proportional. For example, if the addition amount of Cr is 0.05 wt%, the Mg content can be reduced by 0.50 wt% to 1.00 wt%. As an example, if the aluminum alloy contains 0.10 wt% Cr, the Mg content in the aluminum alloy can be reduced by 0.50 wt%. In some examples, the aluminum alloy described herein may include a ratio of Mg to Cr (also referred to herein as a Mg:Cr ratio) that can be 20:1 to 70:1 (e.g., 25:1 to 65:1 or 25:1 to 35:1). For example, the Mg:Cr ratio may be 20: 1, 25: 1, 30: 1, 35: 1, 40: 1, 45: 1, 50: 1, 55: 1, 60: 1, 65: 1, or 70: 1. In some embodiments, including Mg and Cr in the aforementioned ratios may produce an aluminum alloy having good aluminum alloy strength and formability.
[0159] In some examples, the aluminum alloys described herein may include a combined content of Si, Cr, and Cu in an amount greater than 0.35% (e.g., greater than 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, or 0.50%). All expressed in weight %.
[0160] Titanium (Ti)
[0161] In some examples, the aluminum alloys described herein include Ti in an amount of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less, based on the total weight of the alloy. For example, the alloy may include 0.01%, 0.02%, 0.03%, 0.04%, or 0.05% Ti. In some cases, there is no Ti in the alloy (i.e., 0%). All are expressed in weight %.
[0162] Trace Elements
[0163] Optionally, the aluminum alloys described herein may also include other trace elements sometimes referred to as impurities in an amount of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. These impurities may include, but are not limited to, Sc, V, Ni, Hf, Zr, Sn, Ga, Ca, Bi, Na, Pb, or a combination thereof. Thus, Sc, V, Ni, Hf, Zr, Sn, Ga, Ca, Bi, Na, or Pb may be present in the alloy in an amount of 0.05% or less, 0.04% or less, 0.03% or less, 0.02% or less, or 0.01% or less. The sum of all impurities does not exceed 0.15% (e.g., 0.1%). All are expressed in wt %. The remaining percentage of each alloy may be aluminum.
[0164] Recycled content
[0165] The aluminum alloys described herein can tolerate larger amounts of recycled aluminum alloy scrap and still exhibit desired mechanical properties. Impurities are compensated by providing a customized aluminum alloy composition, thereby reducing the impact of impurities and / or alloying elements on the mechanical properties of the aluminum alloy. This enables the production of aluminum alloys that still exhibit desired properties with larger amounts of cheaper, more impure recycled aluminum materials (e.g., used beverage cans). The aluminum alloy composition described herein may include larger amounts of recycled aluminum alloys, which contain little or no additional raw aluminum, and contain a reduced amount of more expensive alloying elements (e.g., Mg).
[0166] In some embodiments, aluminum alloy composition as herein described provides a kind of composition that is very suitable for utilizing waste beverage can (UBC) waste or other aluminum alloy containers as recycled materials.UBC waste is a mixture of various aluminum alloys (e.g., from different aluminum alloys for can body and can end), and can usually contain foreign matter, such as rainwater, beverage residues, organic matter (e.g., paint and laminated film) and other materials.UBC waste usually comprises a mixture of metals from various aluminum alloys, such as metals from can body (e.g., AA3104, AA3004 or other 3xxx series aluminum alloys) and can end (e.g., AA5182 or other 5xxx series aluminum alloys).UBC waste can be shredded and de-coated or depainted before melting, to be used as liquid metal billet when casting new metal products.
[0167] As discussed herein, the aluminum alloy compositions described herein reduce the composition gap between the can body stock and the can end stock. This allows the use of more recycled aluminum alloys, particularly UBC scrap, for the production of can end stock and reduces the amount of primary aluminum and other alloying elements (e.g., Mg). In some aspects, the aluminum alloys described herein contain a large amount of UBC scrap equal to or greater than 25%, such as equal to or greater than 30%, equal to or greater than 35%, equal to or greater than 40%, equal to or greater than 45%, equal to or greater than 50%, equal to or greater than 55%, equal to or greater than 60%, equal to or greater than 65%, equal to or greater than 70%, or equal to or greater than 75%. In terms of range, the aluminum alloys described herein may contain 25% to 100% UBC scrap (e.g., 25% to 95%, 30% to 90%, 35% to 85%, 40% to 80%, 50% to 70%, or 35% to 50%).
[0168] As described above, in some aspects, the UBC scrap includes a mixture of alloys including a 3xxx series aluminum alloy and a 5xxx series aluminum alloy. In some aspects, the UBC scrap may include a 5xxx series aluminum alloy in an amount of 0% to 75% (e.g., 5% to 70%, 10% to 65%, 15% to 60%, 20% to 50%, or 25% to 40%) based on the total weight of the recycled scrap. For example, the UBC scrap may include greater than 0% 5xxx series aluminum alloy scrap (e.g., greater than 1%, greater than 5%, greater than 10%, greater than 15%, greater than 20%, or greater than 25%) based on the total weight of the UBC scrap. All are expressed in weight %.
[0169] In some aspects, the UBC scrap can include 3xxx series aluminum alloy scrap (from mixed aluminum scrap) in an amount of 0% to 75% (e.g., 5% to 70%, 10% to 65%, 15% to 60%, 20% to 50%, or 25% to 40%) based on the total weight of the UBC scrap. For example, the UBC scrap can include greater than 0% 3xxx series aluminum alloy scrap (e.g., greater than 1%, greater than 5%, greater than 10%, greater than 15%, greater than 20%, or greater than 25%) based on the total weight of the UBC scrap. All are expressed in weight %.
[0170] In some aspects, the aluminum alloys described herein include less than 35% primary aluminum, such as less than 34%, less than 33%, less than 32%, less than 31%, less than 30%, less than 29%, less than 28%, less than 27%, less than 26%, less than 25%, less than 24%, less than 23%, less than 22%, less than 21%, or less than 20%. All are expressed in weight %.
[0171] characteristic
[0172] In some examples, the aluminum alloy product (e.g., aluminum alloy sheet) produced by the aluminum alloy described herein can have a yield strength of about 260 MPa or greater. For example, the aluminum alloy product produced by the aluminum alloy described herein can have a yield strength of 270 MPa or greater, 280 MPa or greater, 290 MPa or greater, 300 MPa or greater, 310 MPa or greater, 320 MPa or greater, 325 MPa or greater, 330 MPa or greater, 335 MPa or greater, 340 MPa or greater, 345 MPa or greater, 350 MPa or greater, 355 MPa or greater, 360 MPa or greater, 365 MPa or greater, or 370 MPa or greater. In some cases, the yield strength is from about 260 MPa to about 420 MPa (e.g., from about 280 MPa to about 450 MPa, from about 300 MPa to about 425 MPa, or from about 325 MPa to about 400 MPa), or any value therebetween. The aluminum alloy products described herein may exhibit a yield strength as described herein when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions (each corresponding to the rolling direction).
[0173] In some instances, the aluminum alloy product produced by the aluminum alloy described herein may have an ultimate tensile strength of about 280MPa or greater. For example, the aluminum alloy product may have an ultimate tensile strength of 290MPa or greater, 300MPa or greater, 310MPa or greater, 320MPa or greater, 330MPa or greater, 340MPa or greater, 350MPa or greater, 355MPa or greater, 360MPa or greater, 365MPa or greater, 370MPa or greater, 375MPa or greater, 380MPa or greater, 385MPa or greater, 390MPa or greater, 395MPa or greater, or 400MPa or greater. In some cases, the ultimate tensile strength is about 280MPa to about 550MPa (e.g., about 300MPa to about 500MPa, about 350MPa to about 475MPa, or about 375MPa to about 430MPa), or any value therebetween. The aluminum alloy products described herein may exhibit an ultimate tensile strength as described herein, when measured in the longitudinal (L), transverse (T), and / or diagonal (D) directions (each corresponding to a rolling direction).
[0174] In some examples, the aluminum alloy product produced by the aluminum alloy described herein may have a total elongation of about 4% to 20% (e.g., 4% to 18%, 5% to 16%, 5.5% to 14%, 6% to 12%, or 6.5% to 10%). For example, the aluminum alloy product produced by the aluminum alloy described herein may have a total elongation of about 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, or any value therebetween. When measured in the longitudinal (L), transverse (T) and / or diagonal (D) directions (each corresponding to the rolling direction), the aluminum alloy product described herein may exhibit a total elongation as described herein.
[0175] Method for manufacturing aluminum alloy
[0176] Cast
[0177] The aluminum alloys described herein can be cast into cast products using a direct cooling (DC) process, or can be cast using a continuous casting (CC) process. The casting process is performed according to the standards commonly used in the aluminum industry known to those skilled in the art. The CC process may include, but is not limited to, using a double belt casting machine, a double roll casting machine, or a block casting machine. In some instances, the casting process is performed by a CC process to form a slab, a strip, etc. In some instances, the casting process is a DC casting process to form a cast product.
[0178] Then the cast product, slab or strip can be subjected to further processing steps. Optionally, further processing steps can be used to prepare aluminum alloy products (e.g., sheets, Saudi plates or plates). Such processing steps include but are not limited to homogenization steps, hot rolling steps, cold rolling steps and optional painting steps. The processing steps for cast products are described below. However, using modifications known to those skilled in the art, the processing steps can also be used for casting slabs or strips.
[0179] Homogenization Practice 1
[0180] Homogenization conditions can optimize particle formation in aluminum alloys (e.g., produce a larger number of α-phase particles that can be decomposed into small particles), thereby producing good mechanical properties. Particle size and particle number density determine the formability and performance of aluminum alloys. In some embodiments, the particle size in the aluminum alloy microstructure can be controlled by changing the alloying elements (e.g., adding Cr and reducing Mg), which can promote the transformation of the constituent particles from large particles (e.g., Alx(Fe,Mn)) to α-phase particles (e.g., Al-(Fe,Mn)Si) during homogenization. Therefore, homogenization practices combined with aluminum alloy composition can promote particle decomposition and small particle size in the aluminum alloy microstructure.
[0181] Compared with aluminum alloys that do not contain high content of recycled aluminum alloy materials, aluminum alloys produced from high content of recycled aluminum alloy materials contain a large amount of Fe, Si and / or Mn. For example, aluminum alloys produced from waste beverage cans or other aluminum alloy wastes contain a large amount of Fe, Si and / or Mn. These additional alloying elements result in a number density of larger large particles that are difficult to decompose. Large particles such as Alx (Fe, Mn) particles are difficult to decompose, while α-phase particles can be easily decomposed into smaller particles during the rolling process. Therefore, converting Alx (Fe, Mn) into α-phase particles is beneficial to the good mechanical properties of aluminum alloys.
[0182] Fig.13A Scanning electron microscope (SEM) image showing the microstructure of AA5182 aluminum alloy, Figure 1 B shows an SEM image of the microstructure of a recycling-friendly aluminum alloy, which contains 0.40 wt.% Fe, 0.16 wt.% Si, 0.60 wt.% Mn, 0.07 wt.% Cu, 4.0 wt.% Mg, and the remainder Al. Both alloys are used to produce aluminum alloys for can end billets. The recycling-friendly aluminum alloy is produced from a high content of recycled aluminum alloy materials, while the AA5182 aluminum alloy has a strictly controlled aluminum alloy composition and is produced from a very small amount of recycled aluminum alloy materials. Due to the higher recycled content of the recycling-friendly aluminum alloy, a larger amount of alloying elements is present in the aluminum alloy. For example, the recycling-friendly aluminum alloy contains larger amounts of Si, Mn, and Fe than the AA5182 aluminum alloy. As Fig. 13B As shown, the greater amount of alloying elements present in the recycling-friendly aluminum alloy results in the formation of particles having large sizes (e.g., greater than 5 microns) in the aluminum alloy microstructure. Fig.13A The microstructure of the AA5182 aluminum alloy is shown to include particles with smaller sizes and lower large particle number density. Larger components can negatively affect the properties of the aluminum alloy. For example, larger components lead to poor formability. It was unexpectedly discovered that by changing the alloying elements in the aluminum alloy composition (such as adding Cr and reducing Mg) and homogenizing the aluminum under specific conditions, the particle size in the aluminum alloy microstructure can be controlled to promote the transformation of the constituent particles from large particles to alpha phase particles. For example, changing the aluminum alloy composition to reduce the amount of Mg and adding higher levels of Cr, combined with homogenization, can help transform larger components in the aluminum alloy microstructure into smaller alpha phase particles. For example, the method described herein can transform Al into α-phase particles during homogenization. x The (Fe, Mn) components are converted to alpha phase particles. In some embodiments, the homogenization conditions may help convert large particles to alpha phase particles.
[0183] In some embodiments, the cast product may be heated to a homogenization temperature in the range of about 450°C to about 570°C. For example, the cast product may be heated to a temperature of 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, or 570°C. In some embodiments, the cast product may be homogenized in a homogenization temperature range of 450°C to 570°C (e.g., 500°C to 560°C or 525°C to 550°C) to produce the highest concentration of stable α-phase particles. As described above, the aluminum alloys described herein provide a larger homogenization temperature window to produce α-phase particles. Specifically, homogenizing the aluminum alloys in Tables 6-10 and 16-20 in a homogenization temperature window of 450°C to 570°C can transform the large components in the microstructure of the aluminum alloy into α-phase particles throughout the homogenization temperature range. This advantageously provides for an increased amount of conversion of the macroconstituents to alpha phase particles during homogenization.
[0184] In some embodiments, the heating rate to the homogenization temperature can be about 70°C / hour or less, about 60°C / hour or less, or about 50°C / hour or less. The cast product can then be soaked (i.e., maintained at a specified temperature) for a period of time at the homogenization temperature to form a homogenized product. In some examples, the total time of the homogenization step (including the heating stage and the soaking stage) can be up to about 10 hours. For example, the cast product can be soaked at the homogenization temperature for 10 minutes, 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours.
[0185] Homogenization Practice 2
[0186] In the homogenization step, the cast product may be heated to a homogenization temperature, such as a temperature in the range of about 400°C to about 600°C. For example, the cast product may be heated to a temperature of about 400°C, about 410°C, about 420°C, about 430°C, about 440°C, about 450°C, about 460°C, about 470°C, about 480°C, about 490°C, about 500°C, about 510°C, about 520°C, about 530°C, about 540°C, about 550°C, about 560°C, about 570°C, about 580°C, about 590°C, or about 600°C. In some embodiments, the heating rate to the peak metal temperature may be about 70°C / hour or less, about 60°C / hour or less, or about 50°C / hour or less. The cast product may then be allowed to soak (i.e., maintained at a specified temperature) for a period of time to form a homogenized product. In some examples, the total time for the homogenization step (including the heating phase and the soaking phase) can be up to about 10 hours.
[0187] In some embodiments, the homogenization step described herein may be a two-stage homogenization. The first stage may include heating the cast product to a first homogenization temperature of about 350°C to about 450°C (e.g., 360°C to 440°C, 370°C to 430°C, 380°C to 420°C, or 400°C to 420°C). For example, the cast product may be heated to a temperature of about 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, or 450°C. In some cases, the cast product is heated to a first homogenization temperature of 400°C to 420°C. In some cases, the heating rate to the first homogenization temperature may be about 70°C / hour or less, about 60°C / hour or less, or about 50°C / hour or less. The cast product is then soaked (i.e., maintained at a specified temperature first homogenization temperature) for a period of time. In some cases, the cast product is soaked at the first homogenization temperature for up to 5 hours (e.g., 30 minutes to 5 hours, inclusive). For example, the cast product may be soaked at a first homogenization temperature of 350° C. to 450° C. for 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, or 5 hours. In some embodiments, the cast product may be soaked at a first homogenization temperature of 400° C. to 420° C. for 1 to 2 hours.
[0188] The second stage may include heating the cast product from the first homogenization temperature to a second homogenization temperature of about 450°C to about 550°C (e.g., 460°C to 540°C, 470°C to 530°C, 480°C to 520°C, or 480°C to 510°C). For example, the cast product may be heated to a temperature of about 450°C, about 460°C, about 470°C, about 480°C, about 490°C, about 500°C, about 510°C, about 520°C, about 530°C, about 540°C, or 550°C. In some cases, the cast product is heated to a first homogenization temperature of 480°C to 510°C. The cast product is then soaked for a period of time at the second homogenization temperature. In some cases, the cast product is soaked at the second homogenization temperature for up to 5 hours (e.g., 30 minutes to 5 hours, including end values). For example, the cast product may be soaked at a second homogenization temperature of 450° C. to 550° C. for 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, or 5 hours. In some embodiments, the cast product may be soaked at a second homogenization temperature of 480° C. to 510° C. for 0 to 2 hours.
[0189] Hot Rolling
[0190] After the homogenization step, a hot rolling step can be performed. The homogenized product can be hot rolled using a rolling mill to produce a hot rolled product. Before starting hot rolling, the homogenized product can be cooled to a desired temperature such as about 200°C to about 425°C. For example, the homogenized product can be cooled to a temperature of about 200°C to about 400°C, about 250°C to about 375°C, about 300°C to about 425°C, or about 350°C to about 400°C. The homogenized product can then be hot rolled at a hot rolling temperature, for example, about 200°C to about 450°C, to produce a hot rolled product (e.g., hot rolled plate, hot rolled Saudi plate, or hot rolled sheet).
[0191] Cold Rolling
[0192] The hot rolled product can be cold rolled into a thinner product, such as a final gauge rolled product, using a cold rolling mill. The final gauge rolled product can have a gauge between about 0.5 and about 10 mm, for example, between about 0.7 and about 6.5 mm. Optionally, the final gauge rolled product can have a gauge of about 0.5 mm, about 1.0 mm, about 1.5 mm, about 2.0 mm, about 2.5 mm, about 3.0 mm, about 3.5 mm, about 4.0 mm, about 4.5 mm, about 5.0 mm, about 5.5 mm, about 6.0 mm, about 6.5 mm, about 7.0 mm, about 7.5 mm, about 8.0 mm, about 8.5 mm, about 9.0 mm, about 9.5 mm, or about 10.0 mm. Cold rolling may be performed to obtain a final gauge thickness representing a gauge reduction of up to about 85% (e.g., up to about 10%, up to about 20%, up to about 30%, up to about 40%, up to about 50%, up to about 60%, up to about 70%, up to about 80%, or up to about 85%) compared to the gauge before cold rolling was initiated. In some embodiments, the cold rolling step may include one or more cold rolling steps to achieve the desired gauge thickness reduction. Optionally, the method for producing an aluminum alloy may include an intermediate annealing step (e.g., between one or more cold rolling steps).
[0193] Paint
[0194] Subsequently, the final gauge rolled product may optionally undergo a painting step. The painting step may apply a coating to the final gauge rolled product at a temperature of 150°C to 400°C for 1 second to 10 minutes. For example, the final gauge rolled product may be painted at a temperature of 150°C to 400°C, 200°C to 400°C, 250°C to 350°C, 200°C to 300°C, or 300°C to 400°C. The peak metal temperature of the final gauge rolled product during the painting process may range from 100°C to 300°C (e.g., 125°C to 275°C, 150°C to 250°C, or 200°C to 300°C).
[0195] Aluminum alloy microstructure
[0196] The aluminum alloy described herein contains small particles in the aluminum alloy microstructure. A large number of particles present in the aluminum alloy microstructure have a diameter of 1.45 μm measured by area. 2 For example, the particle size measured by area may be 1.40 μm. 2 or smaller, 1.35μm 2 or smaller, 1.30μm 2 or smaller, 1.25μm 2 or smaller, 1.20μm 2 or smaller, 1.15μm 2 or smaller, or 1.10μm 2 In some examples, the particle size range is 0.80 μm 2 Up to 1.45μm 2 (For example, 0.85 μm 2 Up to 1.40μm 2 or 0.90μm 2 Up to 1.35μm 2 As used herein, "substantial amount" with respect to the number of particles comprises at least 50% of the particles present in the aluminum alloy. For example, at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, at least 95%, or at least 99% of the particles present in the aluminum alloy product have a particle size of 1.45 μm. 2 or smaller particle size.
[0197] The aluminum alloys described herein include alpha-phase particles. In some embodiments, the aluminum alloys described herein include a particle area % of alpha-phase particles measured by volume of 1.5% or more, 1.6% or more, 1.7% or more, 1.8% or more, 1.9% or more, or 2.0% or more. In some embodiments, the aluminum alloys described herein include a particle area % of alpha-phase particles measured by volume of 1.5% to 2.5% (e.g., 1.5% to 2.0%, 2.0% to 2.5%, or 1.7% to 2.1%).
[0198] The aluminum alloys described herein include a ratio of α-phase particles to Alx (Fe, Mn) that advantageously provides good formability characteristics for the aluminum alloy. In some embodiments, the ratio of α-phase particles to Alx (Fe, Mn) in the aluminum alloy microstructure is 5:1 to 40:1 (e.g., 6:1 to 30:1, 8:1 to 25:1, 8:1 to 20:1, or 10:1 to 20:1). In some embodiments, the ratio of α-phase particles to Alx(Fe, Mn) in the aluminum alloy microstructure is 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1, 31:1, 32:1, 33:1, 34:1, 35:1, 36:1, 37:1, 38:1, 39:1, or 40:1.
[0199] Examples of suitable methods and alloy products
[0200] Example 1 is an aluminum alloy comprising 0.10-0.35 wt. % Si, 0.20-0.60 wt. % Fe, 0.05-0.25 wt. % Cu, 0.25-1.20 wt. % Mn, 2.0-5.0 wt. % Mg, up to 0.20 wt. % Cr, up to 0.30 wt. % Zn, up to 0.20 wt. % Ti, up to 0.15 wt. % impurities, and Al.
[0201] Example 2 is an aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises 0.10-0.30 wt. % Si, 0.20-0.50 wt. % Fe, 0.05-0.25 wt. % Cu, 0.30-1.0 wt. % Mn, 2.2-5.0 wt. % Mg, up to 0.15 wt. % Cr, up to 0.30 wt. % Zn, up to 0.15 wt. % Ti, up to 0.15 wt. % impurities, and Al.
[0202] Example 3 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises 0.10-0.25 wt. % Si, 0.20-0.50 wt. % Fe, 0.05-0.25 wt. % Cu, 0.30-0.90 wt. % Mn, 2.5-5.0 wt. % Mg, up to 0.10 wt. % Cr, up to 0.25 wt. % Zn, up to 0.10 wt. % Ti, up to 0.15 wt. % impurities, and Al.
[0203] Example 4 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises 0.20-0.35 wt. % Si, 0.20-0.50 wt. % Fe, 0.05-0.25 wt. % Cu, 0.30-0.90 wt. % Mn, 2.5-5.0 wt. % Mg, up to 0.05 wt. % Cr, up to 0.25 wt. % Zn, up to 0.05 wt. % Ti, up to 0.15 wt. % impurities, and Al.
[0204] Example 5 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises 0.20-0.35 wt. % Si, 0.40-0.60 wt. % Fe, 0.15-0.25 wt. % Cu, 0.60-1.2 wt. % Mn, 2.0-4.0 wt. % Mg, up to 0.03 wt. % Cr, up to 0.20 wt. % Zn, up to 0.03 wt. % Ti, up to 0.15 wt. % impurities, and Al.
[0205] Example 6 is the aluminum alloy of any preceding or subsequent example, wherein the ratio of Mg:Cu is 10:1 to 80:1, and the ratio of Mn:Cu is 2:1 to 15:1.
[0206] Example 7 is the aluminum alloy of any preceding or subsequent example, wherein the ratio of Mg:Cu is 15:1 to 70:1, and the ratio of Mn:Cu is 3:1 to 12:1.
[0207] Example 8 is the aluminum alloy of any preceding or subsequent example, wherein the combined content of Fe and Si is greater than 0.40 wt %.
[0208] Example 9 is the aluminum alloy of any preceding or subsequent example, wherein the combined content of Mg, Mn, and Cu is 3.5 wt % to 5.0 wt %.
[0209] Example 10 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises at least 40 weight percent recycled scrap.
[0210] Example 11 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises less than 30 weight percent primary aluminum.
[0211] Example 12 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy has a thermal conductivity of at least 30.0 KJ / m as measured by ASTM B871-1 (2021). 2 of propagation energy.
[0212] Example 13 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy has a yield strength of at least 340 MPa.
[0213] Example 14 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy has an ultimate tensile strength of at least 380 MPa.
[0214] Example 15 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy has a total elongation of at least 4%.
[0215] Example 16 is a can end stock comprising an aluminum alloy as described in any preceding or subsequent example.
[0216] Example 17 is a method for producing an aluminum alloy, the method comprising: casting an aluminum alloy to form a cast product, wherein the aluminum alloy contains 0.10-0.35 wt. % Si, 0.20-0.60 wt. % Fe, 0.05-0.25 wt. % Cu, 0.25-1.20 wt. % Mn, 2.0-5.0 wt. % Mg, up to 0.20 wt. % Cr, up to 0.30 wt. % Zn, up to 0.20 wt. % Ti, up to 0.15 wt. % impurities and Al; homogenizing the cast product; hot rolling the cast product to produce a hot rolled product; cold rolling the hot rolled product to produce a final specification rolled product; and optionally annealing the final specification rolled product.
[0217] Example 18 is the method of any preceding or subsequent example, wherein the method further comprises painting and curing the final gauge mill product.
[0218] Example 19 is the method of any preceding or subsequent example, wherein the homogenizing step comprises a first homogenizing step and a second homogenizing step.
[0219] Example 20 is the method of any preceding or subsequent example, wherein the first homogenizing step comprises soaking the cast product at a temperature of 375° C. to 450° C. for 0.5 to 5 hours.
[0220] Example 21 is the method of any preceding or subsequent example, wherein the second homogenizing step comprises soaking the cast product at a temperature of 450° C. to 550° C. for 0.01 hour to 5 hours.
[0221] Example 22 is the method of any preceding or subsequent example, wherein the aluminum alloy comprises 0.10-0.25 wt. % Si, 0.20-0.50 wt. % Fe, 0.05-0.25 wt. % Cu, 0.30-0.90 wt. % Mn, 2.5-5.0 wt. % Mg, up to 0.15 wt. % Cr, up to 0.25 wt. % Zn, up to 0.15 wt. % Ti, up to 0.15 wt. % impurities, and Al.
[0222] Example 23 is the method of any preceding or subsequent example, wherein the ratio of Mg:Cu is 15:1 to 70:1, and the ratio of Mn:Cu is 3:1 to 12:1.
[0223] Example 24 is a metal product prepared according to the method of any preceding or subsequent example.
[0224] Example 25 is a metal product prepared according to the method of any preceding or subsequent example, wherein the metal product is a can end blank.
[0225] Example 26 is an aluminum alloy comprising 0.01-0.60 wt. % Si, 0.01-0.80 wt. % Fe, 0.05-0.30 wt. % Cu, 0.80-1.40 wt. % Mn, 1.3-5.0 wt. % Mg, up to 0.20 wt. % Cr, up to 0.30 wt. % Zn, up to 0.05 wt. % Ti, up to 0.15 wt. % impurities, and the remainder Al.
[0226] Example 27 is an aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises 0.10-0.50 wt. % Si, 0.20-0.70 wt. % Fe, 0.11-0.30 wt. % Cu, 0.80-1.00 wt. % Mn, 1.5-5.0 wt. % Mg, up to 0.20 wt. % Cr, up to 0.25 wt. % Zn, up to 0.05 wt. % Ti, up to 0.15 wt. % impurities, and the remainder Al.
[0227] Example 28 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises 0.22-0.32 wt. % Si, 0.50-0.65 wt. % Fe, 0.20-0.30 wt. % Cu, 0.80-0.92 wt. % Mn, 2.0-4.0 wt. % Mg, up to 0.20 wt. % Cr, up to 0.25 wt. % Zn, up to 0.03 wt. % Ti, up to 0.15 wt. % impurities, and the remainder Al.
[0228] Example 29 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises 0.25-0.32 wt. % Si, 0.45-0.55 wt. % Fe, 0.20-0.30 wt. % Cu, 0.80-0.92 wt. % Mn, 2.0-4.0 wt. % Mg, 0.01-0.20 wt. % Cr, up to 0.25 wt. % Zn, up to 0.03 wt. % Ti, up to 0.15 wt. % impurities, and the remainder Al.
[0229] Example 30 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises 0.25-0.35 wt. % Si, 0.45-0.55 wt. % Fe, 0.16-0.30 wt. % Cu, 0.80-0.92 wt. % Mn, 3.0-4.0 wt. % Mg, 0.05-0.15 wt. % Cr, up to 0.25 wt. % Zn, up to 0.03 wt. % Ti, up to 0.15 wt. % impurities, and the remainder Al.
[0230] Example 31 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises 0.05-0.20 wt % Cr.
[0231] Example 32 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy has a Mg:Cr ratio of 20:1 to 70:1.
[0232] Example 33 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy has a combined content of Si, Cr, and Cu greater than 0.35 wt %.
[0233] Example 34 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises a combined content of Fe and Si greater than 0.40 wt %.
[0234] Example 35 is the aluminum alloy of any preceding or subsequent example, wherein the particles in the aluminum alloy microstructure have a particle size of 1.45 μm by area. 2 or smaller particle size.
[0235] Example 36 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises at least 40 weight percent recycled scrap.
[0236] Example 37 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises less than 30 weight percent primary aluminum. In some embodiments, the aluminum alloy has a yield strength of at least 340 MPa.
[0237] Example 38 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises an ultimate tensile strength of at least 380 MPa.
[0238] Example 39 is the aluminum alloy of any preceding or subsequent example, wherein the aluminum alloy comprises a total elongation of at least 4%.
[0239] Example 40 is a can end stock comprising an aluminum alloy as described in any preceding or subsequent example.
[0240] Example 41 is a method for producing the provided aluminum alloy, the method comprising casting the aluminum alloy to form a cast product, wherein the aluminum alloy contains 0.01-0.60 wt. % Si, 0.01-0.80 wt. % Fe, 0.05-0.30 wt. % Cu, 0.80-1.40 wt. % Mn, 1.3-5.0 wt. % Mg, up to 0.20 wt. % Cr, up to 0.30 wt. % Zn, up to 0.05 wt. % Ti, up to 0.15 wt. % impurities and the remainder Al; homogenizing the cast product; wherein the cast product is homogenized to produce α-phase particles; hot rolling the cast product to produce a hot rolled product; cold rolling the hot rolled product to produce a final specification rolled product; and optionally annealing the final specification rolled product.
[0241] Example 42 is the method of any preceding or subsequent example, wherein the aluminum alloy comprises 0.05-0.20 wt % Cr, and wherein the ratio of Mg:Cr is 20:1 to 70:1.
[0242] Example 43 is the method of any preceding or subsequent example, wherein the homogenizing step includes heating and soaking the cast product at a temperature of 450° C. to 570° C., wherein the homogenizing is configured to transform the large particles into alpha phase particles.
[0243] Example 44 is the method of any preceding or subsequent example, wherein the cast product is soaked at the homogenization temperature for up to 10 hours.
[0244] Example 45 is the method of any preceding or subsequent example, wherein the aluminum alloy after homogenization comprises a grain area % of alpha phase grains measured by volume of 1.5% or greater.
[0245] Example 46 is the method of any preceding or subsequent example, wherein the aluminum alloy comprises 0.22-0.32 wt. % Si, 0.50-0.65 wt. % Fe, 0.20-0.30 wt. % Cu, 0.80-0.92 wt. % Mn, 2.0-4.0 wt. % Mg, up to 0.20 wt. % Cr, up to 0.25 wt. % Zn, up to 0.03 wt. % Ti, up to 0.15 wt. % impurities, and the remainder Al.
[0246] The following examples will be used to further illustrate the present invention, but do not constitute any limitation of the present invention. On the contrary, it should be clearly understood that after reading the description herein, those skilled in the art can think of making various other embodiments, modifications and equivalent schemes thereof without departing from the spirit of the present invention.
[0247] During the studies described in the following examples, conventional procedures were followed unless otherwise stated.Some procedures are described below for illustrative purposes.
[0248] Example
[0249] Example 1
[0250] Sample aluminum alloys were tested to determine the properties of the aluminum alloys described herein. Comparative Example 1 and Examples 1-5 were prepared according to the methods described herein. Comparative Example 1 was prepared from a conventional AA5182 aluminum alloy, which is currently used as a can end stock. Examples 1-5 were prepared from the aluminum alloys described herein. Table 21 provides the aluminum alloy composition for each of Comparative Example 1 and Examples 1-5.
[0251]
[0252] As shown in Table 21, Comparative Example 1 contains lower amounts of Si and Fe than Examples 1-5. Although Comparative Example 1 and Example 1 have similar compositions, the differences in Fe and Si in the aluminum alloys used to produce the can end stock are large and can result in significant differences in performance. Comparative Example 1 contains 35 wt.% primary aluminum. Examples 1-4 include 25% to 30 wt.% primary aluminum, and Example 5 includes 20 wt.% primary aluminum. The aluminum alloys described herein contain up to 15 wt.% less primary aluminum than the AA5182 aluminum alloy, which can save significant costs. In addition, Examples 1-5 can incorporate larger amounts of UBC scrap to replace primary aluminum because the aluminum alloys can tolerate larger amounts of Si and Fe.
[0253] Figure 1 A graphical representation of yield strength, ultimate tensile strength, and total elongation is provided for Comparative Example 1 and Examples 1-5. Examples 1-5 exhibit similar yield strength, ultimate tensile strength, and total elongation properties as Comparative Example 1, but with less primary aluminum and higher UBC scrap. In fact, Examples 1-3 exhibit the same or greater yield strength and ultimate tensile strength properties as Comparative Example 1. Examples 1 and 2 also exhibit the same or better total elongation properties as Comparative Example 1. Examples 4 and 5 contain significantly less Mg than Comparative Example 1, and achieve similar yield strength and ultimate tensile strength properties as Comparative Example 1. The additional Mn in Examples 4 and 5 likely contributes to the additional strengthening, compensating for the reduced amount of Mg.
[0254] Figure 2A graphical representation of the yield stress (MPa) measured in the longitudinal (L), transverse (T) and diagonal (D) directions (each corresponding to the rolling direction) for Comparative Example 1 and Examples 1-5 is provided. Comparative Example 1 exhibits a yield stress of about 350 MPa in each of the L, T and D directions. Compared to Comparative Example 1, Examples 2 and 3 exhibit higher yield strengths in the L, T and D directions, but have higher Si and Fe contents. Example 3 has a Mn content of 0.60 wt %, exhibiting the highest yield stress in the L, T and D directions. Examples 3 and 4 each have 4.1 wt % Mg, exhibiting yield stress values comparable to Comparative Example 1, but with less Mg. Example 4 shows that when compared to Comparative Example 1, reducing the Mg content in the alloy composition while increasing the Mn content can achieve comparable yield stresses in the L, T and D directions. In addition, Example 5 shows that increasing the Fe and Si content to increase the recycled content in the alloy composition results in a yield stress also similar to Comparative Example 1. These results show that by increasing the recycled content and replacing Mg with higher levels of Mn, the resulting properties are consistent with currently commercially available aluminum alloys for can end stock.
[0255] Comparative Example 1 and Examples 1, 4 and 5 were evaluated to determine the effects of Fe and Si on the particle number density and particle area % of α particles, Al(Fe,Mn) particles and Mg2Si particles in the aluminum alloy microstructure. Figure 3A and 3B The particle number density and particle area % results for Comparative Example 1 and Examples 1, 4, and 5 are shown. Example 1 contains a greater amount of Si and Fe than Comparative Example 1, having a total particle area % greater than 1.50% of Comparative Example 1. Example 1 exhibits a smaller particle size than Comparative Example 1, but has a higher number density of α, Al(Fe,Mn), and Mg2Si particles. Examples 4 and 5 both have a lower Mg content and a higher Mn content than Comparative Example 1, exhibiting a larger particle size α area % than Comparative Example 1. As discussed herein, increasing the Si and Fe content in an aluminum alloy composition can achieve a higher recovery content. For example, an aluminum alloy composition with increased Si and Fe (such as Example 5) maintains a similar particle size as Example 4, while the particle area of Al(Fe,Mn) increases. In addition, increasing the content of Fe, Si, and Mn while reducing the Mg content (Examples 4 and 5) results in a total particle number density comparable to Comparative Example 1, while significantly increasing the α particle number density and reducing the particle number density of Al(Fe,Mn) and Mg2Si.
[0256] Comparative Example 1 and Examples 1, 4 and 5 samples were made into 1 mm thick rectangular samples for crack extension testing according to the Kahn tear test (ASTM B871-10 (2021)). Using samples with pre-existing cracks, the fracture toughness of the samples was tested by crack extension energy while applying a cyclic load on each side of the crack to extend it. Figure 4 Results of Kahn tear tests for Comparative Example 1 and Examples 1, 4, and 5 are shown. Example 1 has lower propagation energy and higher yield stress relative to Comparative Example 1. In addition, Example 4 has a lower Mg content and higher Si and Fe content than Comparative Example 1, exhibiting lower propagation energy compared to Comparative Example 1 while maintaining relatively similar yield stress. The results show that the aluminum alloy described herein contains a lower amount of Mg and a higher amount of Si and Fe than Comparative Example 1, exhibiting similar propagation energy and yield stress. In addition, the increased amounts of Si, Fe, and Mn combined with the lower level of Mg further increase the recycled content of the aluminum alloy while still providing comparable properties to the current AA5182 aluminum alloy.
[0257] Examples 1 and 2 were evaluated to determine the effect of Mn on the particle number density and particle area % of α particles, Al(Fe,Mn) particles, and Mg2Si particles in the aluminum alloy microstructure. Figure 5A and 5B A graphical representation of the particle area % and particle number density of alpha particles, Al(Fe,Mn) particles, and Mg2Si particles in the microstructures of Examples 1 and 2 is provided. Example 1 includes 0.16 wt% Si, 0.40 wt% Fe, and 0.33 wt% Mn, while Example 2 includes the same amounts of Si and Fe, and a higher Mn content of 0.60 wt%. Example 2 exhibits larger particle sizes and particle areas of alpha particles and Al(Fe,Mn) particles than Example 1. The greater amount of Mn in Example 2 increases the particle number density compared to Example 1.
[0258] Figure 6 The results of the Kahn tear test (ASTM B871-10 (2021)) of Examples 1 and 2 are shown. Example 1 has a tear strength of 38.8 KJ / m 2 The propagation energy and yield stress of about 360MPa, Example 2 has 34.4KJ / m 2 Example 2 has a higher Mn content than Example 1, and exhibits lower propagation energy and higher yield stress than Example 1.
[0259] Examples 2 and 3 were evaluated to determine the effect of Mg on the particle number density and particle area % of alpha particles, Al(Fe,Mn) particles, and Mg2Si particles in the aluminum alloy microstructure. Fig. 7A and 7B A graphical representation of the particle area % and particle number density of alpha particles, Al(Fe,Mn) particles, and Mg2Si particles in the microstructures of Examples 2 and 3 is provided. Example 3 contains a lower Mg content (4.1 wt %) than Example 2 (4.9 wt %). Example 3 has a particle size of approximately 2.4 μm. 2 The particle size of Example 3 is 0.0447 W and the particle area is about 2%, which is consistent with Comparative Example 1. Example 3 has a smaller particle size and a smaller area fraction of Al(Fe,Mn) than Example 2. By changing the Mg content from 4.9 wt % (Example 2) to 4.1 wt % (Example 3), the particle number density of α particles increases, while the particle number densities of Al(Fe,Mn) and Mg2Si both decrease.
[0260] Figure 8 The results of the Kahn tear test (ASTM B871-10 (2021)) for Examples 2 and 3 are shown. Alloy Example 2 has a tensile strength of 34.4 kJ / m 2 The propagation energy and yield stress of about 375MPa. Example 3 has a lower Mg content than Example 2, with 36.1KJ / m 2 of propagation energy, and a yield stress of about 360MPa.
[0261] Examples 1, 3 and 4 were evaluated to determine the effects of Mg and Mn on the particle number density and particle area % of α particles, Al(Fe,Mn) particles and Mg2Si particles in the aluminum alloy microstructure. Fig. 9A and 9B A graphical representation of the particle area % and particle number density of α particles, Al(Fe,Mn) particles, and Mg2Si particles in the microstructure of Examples 1, 3, and 4 is provided. Example 3 has a lower Mg and higher Mn content than Example 1, and has a higher α particle area fraction and a lower Al(Fe,Mn) and Mg2Si particle area fraction than Example 1. In addition, as the Mg content decreases, the particle size of Examples 3 and 4 is larger relative to Example 1. In addition, it is found that after replacing Mg with Mn, the total particle area of each of Examples 1, 3, and 4 is almost the same; however, Examples 3 and 4 show an increased α area % and a lower Mg2Si area % compared to Example 1. Although the particle number density of Examples 3 and 4 is lower relative to the examples, the particle size of Examples 3 and 4 is larger.
[0262] Fig.10The results of the Kahn tear test (ASTM B871-10 (2021)) of Examples 1, 3 and 4 are shown. Example 1 has a tear strength of 38.8 KJ / m 2 The propagation energy and yield stress of about 360 MPa are shown in Examples 3 and 4, which have less Mg and more Mn than Example 1, and exhibit similar propagation energy and yield stress characteristics. Specifically, Example 3 has 36.1 KJ / m 2 The propagation energy and yield stress of about 355MPa. Example 4 has 32.2KJ / m 2 The results show that the aluminum alloys described herein (containing lower amounts of Mg and higher amounts of Mn) exhibit similar propagation energies. Furthermore, the results show that the alloy composition can be increased by increasing Mn, Si, and Fe to compensate for the lower Mg content, thereby increasing the recycled content while still maintaining comparable physical properties to the AA5182 aluminum alloy.
[0263] Comparative Example 1 and Examples 1-5 were made into 1 mm thick discs to test the formability using the micro expansion test according to ISO 16808 (2022). Fig.11 The results of the micro-expansion tests of Comparative Example 1 and Examples 1-5 are shown. For example, Comparative Example 1 has an average failure strain of 0.170, while Example 1, which has a higher Fe and Si content, has a relatively comparable average failure strain of 0.168. In addition, Example 2 has a higher Mn content than Comparative Example 1, and shows no change in the average failure strain when compared to Example 1. In addition, by reducing the Mg content to 4.1% by weight provided in Example 3, the average failure strain value is increased to 0.176. As provided in Example 4, further reducing the Mg content while increasing the Mn content reduces the average failure strain to 0.137. In addition, by maintaining the same level of Mn and Mg as Example 4 and increasing the content of Fe and Si, Example 5 exhibits an average failure strain of 0.161, which is similar to Comparative Example 1. The results shown here show that by changing the alloy composition to contain a smaller amount of Mg and increasing the content of Fe, Si and Mn, the same physical properties as Comparative Example 1 can be maintained while significantly increasing its recycling content.
[0264] Example 2
[0265] Sample aluminum alloys were tested to determine the properties of the aluminum alloys described herein. Comparative Examples 2 and 3 and Examples 7 and 8 were prepared according to the methods described herein. Comparative Example 1 was prepared from a conventional AA3104 aluminum alloy, which is currently used as can body stock, and Comparative Example 2 had a composition similar to that of the AA3104 aluminum alloy, but with a lower Mg content. Examples 7 and 8 are alloys containing Fe, Si, Cu, and Mn contents similar to those of the AA3104 aluminum alloy, but with a greater amount of Mg. Table 22 provides the aluminum alloy composition of each of Comparative Examples 2 and 3 and Examples 7 and 8.
[0266]
[0267]
[0268] like Fig.12 As shown, Examples 7 and 8 achieve a buckling strength equal to or greater than 600 kPa. The buckling strength was measured using an end buckling test bench (from Altek, Model 9009H4). Examples 7 and 8 have similar compositions to Comparative Examples 7 and 8, but have a higher Mg content. Since Examples 7 and 8 have similar compositions to Comparative Example 7 (which is an AA3104 aluminum alloy), these aluminum alloys can be produced from larger amounts of recycled UBC scrap containing similar amounts of Fe, Si, Cu, and Mn. This eliminates the need to dilute the aluminum alloys of Examples 7 and 8 with raw aluminum or to add additional hardening elements. In one example, in order to produce an aluminum alloy composition from recycled UBC, at least 2 weight % Mg can be added to cast an alloy composition having a similar level of Fe, Si, Cu, and Mn levels to those in UBC, as shown in Examples 7 and 8 in Table 21. In addition, by maintaining an aluminum alloy composition similar to that of the AA3104 aluminum alloy, the remelting process can be simplified to reduce process changes during manufacturing. The aluminum alloy compositions of Examples 7 and 8 have similar Fe, Si, Cu and Mn as conventional aluminum alloys for can body stock and can end stock, which makes the remelting process much simpler and makes it a full cycle without changing the alloy. In addition, the recycling content will be significantly higher because the demand for primary aluminum or hardening elements is greatly reduced. In contrast, conventional AA5182 aluminum alloys need to be diluted with Fe, Si, Cu, Mn, and a large amount of Mg is added to be cast by UBC.
[0269] Example 3
[0270] Sample aluminum alloys were studied to determine the microstructure of the aluminum alloys described herein when prepared as specified homogenization conditions. Examples 9-12 are alloys described herein containing various amounts of Mg and Cr. Table 23 provides the aluminum alloy composition for each of Examples 9-12.
[0271]
[0272]
[0273] Standard thermodynamic calculations were performed on Examples 9-12 using Thermo-Calc software (trade name, provided by Thermo-Calc Software AB) to screen the effect of varying the aluminum alloy composition on the alpha phase transformation during homogenization. Figures 14A-14D The equilibrium phase fraction diagram for Examples 9-12 is shown. The x-axis represents the homogenization temperature (°C) and the y-axis represents the volume fraction (mol) of different particles in the aluminum alloy. The green line represents the α-phase particles (Al6Mn) and the yellow line represents Mg2Si. The dark blue line represents the liquidus temperature of the aluminum alloy (e.g., the temperature at which the aluminum alloy begins to melt). The gray shaded area represents the homogenization temperature window when the α-phase particles in the aluminum alloy are stable. Figures 14A-14D The effect of aluminum alloy composition on the homogenization temperature window for producing α-phase particles is shown. Fig.14A It is shown that Example 9 has a very narrow homogenization temperature window for producing stable α-phase particles, which ranges from about 550° C. to about 600° C. However, a large portion of the homogenization temperature window overlaps with the liquidus temperature when the aluminum alloy melts, which is undesirable. This greatly limits the homogenization temperature range for producing α-phase particles. Fig.14A It is shown that aluminum alloys produced from large amounts of recycled aluminum alloy materials have a narrow homogenization temperature window to produce α-phase particles, thereby limiting the amount of α-phase in the aluminum alloy.
[0274] Fig. 14B -D proves that the stability of the α phase can be enhanced by changing the alloying elements provided in Examples 9-12. Specifically, Fig. 14B The effect of reducing Mg on the homogenization temperature window compared to Example 9 is shown, Fig. 14C The effect of adding Cr on the homogenization temperature window compared to Example 9 is shown. Fig. 14B The combined effect of reducing Mg and adding Cr on the homogenization temperature window compared to Example 9 is shown. Each of Examples 10-12 has a larger homogenization temperature window to produce alpha phase particles. This provides a larger amount for the phase transformation from the bulk component to the alpha phase. Homogenization at a temperature within the alpha stable region can result in a phase transformation from Alx(Fe,Mn) to the alpha phase. Fig.14A -D, it was unexpectedly discovered that the particle size of aluminum alloys produced from bulk recycled aluminum materials can be controlled by varying the alloying elements and performing homogenization at a temperature that promotes the transformation of the bulk constituents into alpha phase particles.
[0275] also, Fig. 14B It is shown that by reducing Mg, the homogenization temperature range is wider to produce stable α-phase particles. Similarly, Fig. 14CIt is shown that the homogenization temperature range for aluminum alloys containing Cr is even larger to produce stable α-phase particles. Fig.14D The homogenization temperature range for aluminum alloys containing Cr and less Mg is shown to have the largest homogenization window to produce stable α-phase particles. As discussed herein, α-phase particles are advantageous because they can be decomposed into smaller particles because the α-phase particles include eutectic formations that decompose during hot rolling. Even if the volume fraction of the particles increases, the particle size will be significantly smaller. In contrast, Al(Fe, Mn) is a very large and hard particle that is difficult to decompose. In some embodiments, a homogenization temperature range of 450°C to 570°C (e.g., 500°C to 560°C or 525°C to 550°C) produces the highest concentration of stable α-phase particles.
[0276] Example 4
[0277] Sample aluminum alloys were tested to study the amount and size of particles in the microstructure of the aluminum alloys described herein when prepared according to the methods described herein. Examples 13-16 are alloys containing various amounts of Si, Cu, Mg, and Cr. Table 24 provides the aluminum alloy composition for each of Examples 13-16.
[0278]
[0279] Fig.15A and 15B The effect of the aluminum alloy composition on the particle area (%) and average particle size in the microstructure in Examples 13-16 is shown. Fig.15A As shown, Example 13 has the largest amount of Alx(Fe,Mn) particles, which are large components and difficult to decompose during rolling, and the smallest amount of α-phase particles. Fig. 15B It is also shown that Example 13 has a maximum average particle size of about 1.50 square microns. Example 14 contains a larger amount of Si than Example 13, but has 50% less Alx(Fe,Mn) particles than Example 13. In addition, Example 13 has an average particle size of about 1.45 square microns. The data shows that adding Si to the aluminum alloy composition can lead to more α phase transformation and smaller average particle size in the aluminum alloy microstructure.
[0280] In addition, Example 15 shows the effect of adding Cu, and Example 16 shows the effect of reducing Mg and adding Cr on the particle area (%) and average particle size in the aluminum alloy microstructure. In each of Examples 15 and 16, the particle area (%) of α-phase particles is greater than 1.8% by weight. Examples 15 and 16 both have almost no to no Alx (Fe, Mn) particles. The ratio of α-phase particles to Alx (Fe, Mn) particles in Examples 15 and 16 is higher than that in Examples 13 and 14, and Example 16 has almost no Alx (Fe, Mn) particles in the aluminum alloy microstructure. Examples 15 and 16 also have particles less than 1.30 square microns. The examples show that adding Si, Cu, Cr and reducing Mg can advantageously convert large components into α-phase particles during homogenization. Specifically, Example 16 has lower Mg and additional Cr, resulting in a higher particle area % of α-phase particles and a minimum average particle size.
[0281] All patents, publications and abstracts cited above are incorporated herein by reference in their entirety. In order to achieve the various objects of the present invention, various embodiments of the present invention have been described. It should be appreciated that these embodiments are only intended to illustrate the principles of the present invention. Various modifications and alterations thereof will be apparent to those skilled in the art without departing from the spirit and scope of the present invention as defined in the following claims.
Claims
1. An aluminum alloy comprising 0.10-0.35 wt. % Si, 0.20-0.60 wt. % Fe, 0.05-0.25 wt. % Cu, 0.25-1.20 wt. % Mn, 2.0-5.0 wt. % Mg, up to 0.20 wt. % Cr, up to 0.30 wt. % Zn, up to 0.20 wt. % Ti, up to 0.15 wt. % impurities, and Al.
2. The aluminum alloy of claim 1, comprising 0.10-0.30 wt. % Si, 0.20-0.50 wt. % Fe, 0.05-0.25 wt. % Cu, 0.30-1.0 wt. % Mn, 2.2-5.0 wt. % Mg, up to 0.15 wt. % Cr, up to 0.30 wt. % Zn, up to 0.15 wt. % Ti, up to 0.15 wt. % impurities, and Al.
3. The aluminum alloy of claim 1, comprising 0.10-0.25 wt. % Si, 0.20-0.50 wt. % Fe, 0.05-0.25 wt. % Cu, 0.30-0.90 wt. % Mn, 2.5-5.0 wt. % Mg, up to 0.10 wt. % Cr, up to 0.25 wt. % Zn, up to 0.10 wt. % Ti, up to 0.15 wt. % impurities, and Al.
4. The aluminum alloy of claim 1, comprising 0.20-0.35 wt. % Si, 0.20-0.50 wt. % Fe, 0.05-0.25 wt. % Cu, 0.30-0.90 wt. % Mn, 2.5-5.0 wt. % Mg, up to 0.05 wt. % Cr, up to 0.25 wt. % Zn, up to 0.05 wt. % Ti, up to 0.15 wt. % impurities, and Al.
5. The aluminum alloy of claim 1 comprising approximately 0.20-0.35 wt. % Si, 0.40-0.60 wt. % Fe, 0.15-0.25 wt. % Cu, 0.60-1.2 wt. % Mn, 2.0-4.0 wt. % Mg, up to 0.03 wt. % Cr, up to 0.20 wt. % Zn, up to 0.03 wt. % Ti, up to 0.15 wt. % impurities, and Al.
6. The aluminum alloy of any one of claims 1-5, wherein the ratio of Mg:Cu is 10:1 to 80:1, and wherein the ratio of Mn:Cu is 2:1 to 15:
1.
7. The aluminum alloy of any one of claims 1-6, wherein the ratio of Mg:Cu is 15:1 to 70:1, and wherein the ratio of Mn:Cu is 3:1 to 12:
1.
8. The aluminum alloy of any one of claims 1-7, wherein the combined content of Fe and Si is greater than 0.40 wt.%.
9. The aluminum alloy of any one of claims 1-8, wherein the combined content of Mg, Mn and Cu is 3.5 wt.% to 5.0 wt.%.
10. The aluminum alloy of any one of claims 1-9, wherein the aluminum alloy comprises at least 40 weight percent recycled scrap.
11. The aluminum alloy of any one of claims 1-10, wherein the aluminum alloy comprises less than 30 weight percent primary aluminum.
12. The aluminum alloy of any one of claims 1 to 11, wherein the aluminum alloy has a thermal conductivity of at least 30.0 KJ / m as measured by ASTM B871-1 (2021). 2 of propagation energy.
13. The aluminum alloy of any one of claims 1-12, wherein the aluminum alloy has a yield strength of at least 340 MPa.
14. The aluminum alloy of any one of claims 1-13, wherein the aluminum alloy has an ultimate tensile strength of at least 380 MPa.
15. The aluminum alloy of any one of claims 1-14, wherein the aluminum alloy has a total elongation of at least 4%.
16. A can end stock comprising the aluminum alloy according to any one of claims 1 to 15.
17. A method for producing an aluminum alloy, the method comprising: Casting an aluminum alloy to form a cast product, wherein the aluminum alloy comprises 0.10-0.35 wt % Si, 0.20-0.60 wt % Fe, 0.05-0.25 wt % Cu, 0.25-1.20 wt % Mn, 2.0-5.0 wt % Mg, up to 0.20 wt % Cr, up to 0.30 wt % Zn, up to 0.20 wt % Ti, up to 0.15 wt % impurities, and Al; Homogenization of casting products; hot rolling the cast product to produce a hot rolled product; cold rolling the hot rolled product to produce a final specification rolled product; as well as The final gauge rolled product is optionally annealed.
18. The method of claim 17 further comprising painting and curing the final gauge mill product.
19. The method of any one of claims 17 or 18, wherein the homogenization step comprises a first homogenization step and a second homogenization step.
20. The method of claim 19, wherein the first homogenizing step comprises soaking the cast product at a temperature of 375°C to 450°C for 0.5 to 5 hours.
21. The method of claim 19, wherein the second homogenizing step comprises soaking the cast product at a temperature of 450°C to 550°C for 0.01 to 5 hours.
22. The method of any one of claims 17-21, wherein the aluminum alloy comprises 0.10-0.25 wt. % Si, 0.20-0.50 wt. % Fe, 0.05-0.25 wt. % Cu, 0.30-0.90 wt. % Mn, 2.5-5.0 wt. % Mg, up to 0.10 wt. % Cr, up to 0.25 wt. % Zn, up to 0.10 wt. % Ti, up to 0.15 wt. % impurities, and Al.
23. The method of any one of claims 17-22, wherein the ratio of Mg:Cu is from 15:1 to 70:1, and wherein the ratio of Mn:Cu is from 3:1 to 12:
1.
24. A metal product, wherein the metal product is produced by a method comprising any one of claims 17-23.
25. The metal product of claim 24, wherein the metal product is a can end stock.